Social Work’s Constrained Influence over Police: A Historical Analysis of Social Work–Police Relations in the Field of Charities and Corrections, 1874–1982 - Bakko, Matthew; Jacobs, Leah A.; Fixler, Alex; Murray, Bethany Jo; Leotti, Sandra; Erwin, Jennifer; Allen, Elizabeth; Tomczak, Stephen Monroe; Hostetter, C. Riley (Social Service Review, 2026)
Keywords: dept.swk

Peer support to address mental health, social determinants of health, financial wellness, and reentry navigation - Bellamy, Chyrell D.; Flanagan, Elizabeth H.; Hoffler, Stephen; Acevedo, Sophia; Ocasio, Giancarlo; Brisola, Elizabeth; Barone, Kayla; Kitaneh, Razi; Blackman, Kimberly D.; Williamson, Bridgett; Benedict, Patricia; Perry, Trevor; et al. (Frontiers in Health Services, 2026)
IntroductionIncarceration in the United States disproportionately affects individuals with mental illness and substance use disorders and often exacerbates mental health conditions due to the trauma of arrest, separation, disrupted care, and stigma. Forensic Peer Support (FPS) can improve recovery outcomes by building unique trust and rapport that supports community reintegration and recovery outcomes.MethodThis paper describes findings from a qualitative study of 22 participants who are a sub-sample of the larger Recovery Finance study, a multi-level community based participatory research study designed to reduce financial hardships of individuals involved in criminal justice with mental health challenges through system level interventions as well as an individual intervention (randomized control trial testing one-on-one financial capability support (FCS) versus FCS plus forensic peer support). The focus of this paper is the mental health and peer support experiences of the qualitative sub-sample.ResultsThematic analysis of in-depth qualitative interviews revealed the following themes: 1. The Impact of Incarceration, Trauma, and Mental Health, 2. Systemic Failings in Mental Health Care in Prison and Post-Release, 3. The Cycle of Financial Strain and Mental Health, and 4. The Unique Value of Shared Lived Experience through Peer Support. Results highlight the trauma and psychological impact of incarceration, systemic failures in treatment, financial stress as a dominant source of anxiety, often perpetuating cycles of poverty and criminal activity, and the critical role of supportive relationships, in particular FPS.DiscussionThese findings point to the need for integrated models in which forensic peer support is embedded within financial wellness and reentry services.
Keywords: dept.swk; financial wellness; incarceration; mental health; peer support; recovery

Virtual aid: a transformation of group mutual aid - Rodriguez-Keyes, Elizabeth; Cormier, Lisa (Journal of Baccalaureate Social Work, 2025)
Keywords: Chemistry; Computer science; Group (periodic table); Mathematics; Mutual aid; Physics; Political science; Pure mathematics; Transformation (genetics); Transformation group; dept.swk

“We Do This Work Together”: Stigma Negotiation and Resistance in the Lives of Male Sex Workers Who Perform Sex Work Online in the United States - Cifuentes, Alberto; Mogro-Wilson, Cristina; Fendrich, Michael; Quinn, Diane; Rodriguez-Diaz, Carlos (The Journal of Sex Research, 2026)
Keywords: Cognitive reframing; Harm; Men who have sex with men; Mental health; Narrative; Psychological intervention; Resistance (ecology); Sex work; Stigma (botany); dept.swk

Song of my Soul: A Memoir - Rakfeldt, Jaak (Mascot Books, 2025)
An Estonian saying holds that everyone has a unique song in their heart. This profound theme resonates throughout the pages of Song of my Soul. This work is not merely a memoir but a visceral journey through the heart of a besieged nation and a family’s unwavering struggle for survival. Rakfeldt’s narrative immerses the reader in the turbulent twentieth century, when Estonia became a pawn in Stalin and Hitler’s brutal power plays, marked by the devastating impact of three successive occupations. The author recounts his family’s harrowing escape to Sweden, their flight through Europe, and the process of building a new life in the West. He weaves together poignant episodes from his parents’ lives in Estonia, which were shattered by the Soviet invasion, forcing them to flee into forests and marshes and live as partisans hunted by Russian death squads. Beyond the historical account, Song of my Soul is a deeply personal journey. Rakfeldt begins to reclaim his ancestral heritage and fill the void left by displacement and loss. He grapples with questions of identity and belonging. This book serves as a testament to the resilience of refugee families and chronicles the suffering of the Baltic people. It resonates with anyone who has faced immigration challenges and with those seeking to understand the lasting strength of the human spirit.
Keywords: dept.swk

From the guest editor: what is a Festschrift? By Lorrie Greenhouse Gardella - Gardella, Lorrie (Social Work With Groups, 2025)
Keywords: Climate change; Greenhouse; Greenhouse effect; Greenhouse gas; Work (physics); dept.swk

Exploring Black Maternal Suicidal Ideation: A Pilot Study Exploring Risk and Protective Factors for Perinatal Suicidal Thoughts in Black Women - Welz, Natasha (Journal of Racial and Ethnic Health Disparities, 2025)
Keywords: Black women; Exploratory research; Feeling; Mental health; Occupational safety and health; Postpartum period; Pregnancy; Public health; Racism; Suicide prevention; dept.swk

“Not Just on the Sideline”: A Phenomenological Study of Disability, Belonging, and Exclusion - Gackenheimer, Christopher; Garrison, Brianna (Children & Schools, 2025)
Keywords: Identity (music); Inclusion (mineral); Inclusion–exclusion principle; Interpretative phenomenological analysis; Mainstream; Mainstreaming; Psychology of self; Qualitative research; Special education; adolescents; belonging; dept.swk; disability; inclusion; special education

Developing online considerations for the IASWG standards on Social Work with Groups: a tribute to Charles Garvin - Macgowan, Mark; Gardella, Lorrie; Simon, Shirley; Prinsloo, Reineth; van Baar, Huub; Seck, Mamadou; Astray, Andrés; Cañizares, Catalina; Muskat, Barbara (Social Work With Groups, 2025)
Keywords: Charles D. Garvin; Criminology; Engineering; Environmental ethics; IASWG standards for social work practice with groups; Law; Philosophy; Political science; Psychoanalysis; Psychology; Social work; Sociology; Tribute; Work (physics); dept.swk; group work; internationalization; online practice; social work with groups; translation; virtual practice

Self-Concept Among Formerly Incarcerated Sexual Minority Women - Stone, Al; Smoyer, Amy; D’Angelo, Karen (Social Sciences, 2025)
Sexual minority women (SMW) are a resilient yet vulnerable population who may experience poor psychosocial outcomes due to minority stress associated with their marginalized status and traumatic experiences resulting from interpersonal and structural violence. When SMW are incarcerated, the trauma of this experience can exacerbate existing mental health challenges. Self-concept is a key measure of mental health that is associated with increased self-efficacy and positive psychosocial outcomes. This analysis explores the ways in which incarceration impacts the self-concept of SMW. Secondary data analysis of three qualitative interviews with formerly incarcerated SMW was conducted. Specifically, Gilligan’s Listening Guide was used to create “I poems” that articulate the participants’ narratives and contrapuntal voices. These poems were then analyzed to build knowledge about participants’ self-concept. This analysis informs our understandings of self-concept among SMW, violence against women, the vulnerability of binary constructs, and the ways in which people negotiate past, present and future selves. The findings can inform interventions that seek to mitigate the psychosocial risks faced by SMW and formerly incarcerated people and improve outcomes for these populations.
Keywords: Clinical psychology; Developmental psychology; LGBT; Listening Guide; Psychology; Sexual minority; Sexual orientation; Social psychology; dept.swk; incarceration; lesbian; qualitative; self-concept; sexual minority women; transgender

Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Perceived Religious Social Support in Faith Communities for Caregivers of Persons Living with Dementia - Garrison, Brianna; Myers, Dennis; Parrish, Danielle; Oxhandler, Holly (Journal of Gerontological Social Work, 2025)
Keywords: Dementia; Faith; Gerontology; Medicine; Psychology; Psychotherapist; Social support; caregiver; dept.swk; faith community; peer-reviewed; social determinants of health; social support

From Townsend and Malthus to the Poor Law Report: An Examination of the Influence of Ideas Concerning the Relationship of Public Aid and Reproduction on Policy Development, 1786-1834 - Tomczak, Stephen Monroe (Journal of Sociology and Social Work, 2015)
Keywords: dept.swk

Food systems in correctional settings: a literature review and case study - Smoyer, Amy B.; Kjær Minke, Linda (World Health Organization. Regional Office for Europe, 2015)
Food is a central component of life in correctional institutions and plays a critical role in the physical and mental health of incarcerated people and the construction of prisoners’ identities and relationships. An understanding of the role of food in correctional settings and effective management of food systems may improve outcomes for incarcerated people and help correctional administrators to maximize the health and safety of individuals in these institutions. This report summarizes existing research about food systems in correctional settings and provides examples of food programmes in prison and remand facilities, including a case study of food-related innovation in the Danish correctional system. Specific conclusions are offered for policy-makers, administrators of correctional institutions and prison food services professionals,and ideas for future research are proposed.
Keywords: dept.swk

Seeing Through the Eyes of the Other Using Process Recordings - Schneider, Dana A.; Rodriguez-Keyes, Elizabeth; Keenan, Elizabeth King (Clinical Supervision Activities for Increasing Competence and Self-Awareness, 2014)
This chapter describes a two-step process including videotaping and process-recording activities to facilitate self-awareness and the expression of empathy and acceptance toward other points of view. These activities are designed for beginning student clinicians who are currently completing their coursework and their first clinical internship. The first step of videotaping helps clinicians become more aware of their inner thoughts, feelings, beliefs, and personal values. This first step also helps participating clinicians become more aware of their nonverbal communication with clients, helping them assess how their internal experiences of empathy and acceptance match what is being conveyed nonverbally to their clients. The second step of the activity, process recording, helps clinicians reflect on their ability to use self-awareness to analyze their inner experiences and their outer expressions of empathy and acceptance (both verbal and nonverbal) while still being attuned to their clients' communication.
Keywords: dept.swk; nonverbal communication; process-recording activities; self-awareness; videotaping

Group Work Around the Globe: Creating transformative connections in challenging times - Wilkins, Christine; Doel, Mark; Skolnik, Sari; Genke, John; Gardella, Lorrie Greenhouse (Whiting & Birch Ltd, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Coffee Cup - Gardella, Lorrie Greenhouse (Social Work in 42 Objects (and More), 2017)
Can the story of social work be told through Objects? Might a collection of objects be more illuminating than a formal text book or a dry definition? In this engaging, photographic book, Mark Doel curates a collection of 127 objects contributed by people from around the globe to evoke a sense of social work - past, present and future. Written as a Guide to an Exhibition of Social Work, this is the ideal book to introduce social work to newcomers, and to entertain those with long experience of the profession. The objects are presented by a diverse group of people with different perspectives on social work, but with a common imagination.--From publisher.
Keywords: Political Science / Public Policy / Social Services & Welfare; Social Science / Social Work; dept.swk

Introduction to Klaus-Martin Ellerbrock, Theses on Working with Refugees in Germany: Considering the Experiences of Louis Lowy - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Introduction to Olga Derkachova, Children of War: Exploring the Trauma of War through Collective Creative Writing in Literary Workshops - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Exploring the Science of Conducting Surveys for Studying Men’s Sexual Assault Perpetration Behaviors - Aguilar, Jemel; Mahapatra, Neely; Busch-Armendariz, Noël; Dinitto, Diana M. (Journal of Aggression, Maltreatment & Trauma, 2016)
Focus groups were used to explore the most appropriate ways to conduct survey research about men’s relationships with women and their sexual assault behaviors that result in high response rates and decrease socially desirable answers. A racially diverse group of 24 English-speaking heterosexual men, aged 18 years or older, were recruited for participation in 3 focus groups. The men were asked to review a survey instrument used in a previous study and the results from that study. Analysis of the focus group transcripts indicates that the men responded to the survey instrument from 3 distinct perspectives: (a) perpetrators, (b) victims, and (c) respondents. From these perspectives, the men also commented on participant anonymity, survey construction and delivery method, question wording, and potential pitfalls in asking men about sexual assault.
Keywords: Engaging men; dept.swk; rape or sexual assault; survey methodology

Everyone’s responsibility: Community partnerships and shared commitment for mental health promotion - Jung, Hyejin; Aguilar, Jemel P. (Social Work in Mental Health, 2016)
In this article, we use qualitative methods to understand the ways in which community involvement in a community-based mental health promotion conference encourages mental health care in an African-American community. We collected data through key informant interviews, focus groups, and participant observations at conference planning meetings and conferences, as well as archival documents related to the conference. We identify community partnerships and shared commitment as drivers of the outreach to people in the community, creators of a culturally relevant and supportive environment for mental health education, and, consequently, promoters of mental health care in the African-American community.
Keywords: African Americans; case studies; community partnerships; community-based programs; dept.swk; mental health and illness; mental health promotion

HIV Knowledge, Risk Behavior, Stigma, and Their Impact on HIV Testing among Asian American and Pacific Islanders: A Review of Literature - Sen, Soma; Nguyen, Hoang Dung; Kim, So Yung; Aguilar, Jemel (Social Work in Public Health, 2017)
Asian American and Pacific Islanders (AAPIs) are the fastest growing population in the United States with documented increases in HIV rates. AAPIs are as likely as other racial/ethnic groups to engage in HIV-related risk behaviors, while being concomitantly less likely to have been HIV tested. Testing is a critical step in HIV prevention. Research points to various barriers to HIV-related testing including HIV knowledge and attitude and stigma. However, these factors and their impact among AAPIs are poorly understood. Myths about this population's “model minority” status compound AAPIs' sociocultural factors including English language proficiency, access to healthcare, and a culture of “silence” that negatively influences HIV-related research. In this article, the authors review the scientific literature on knowledge, risk behavior, and stigma to document the current state of research. Based on the review the authors offer a set of research, policy, and practice recommendations for social workers and other service providers working with AAPIs.
Keywords: HIV and AAPI; Social epidemiology of HIV/AIDS; dept.swk; health disparities and HIV/AIDS

Migration and HIV among Asian Populations: Social Work interventions - Sen, S; Aguilar, Jemel (Migrant Workers: Social Identity, Occupational Challenges and Health Practices, 2016)
Worldwide labor migration has transformed and reshaped various fields of government policy and professional practices. Labor migration is associated with the non-economic social phenomena that scholars have increasingly paid attention to in both sending and receiving destinations. For practitioners in the field of education, medicine, nursing, social work, mental health, public health, and other professional practices, the human face of labor migration migrant workers and their families daily challenges often reveals the human cost of migration behind the image of economic gain and benefits. Migrant workers and their families are facing vexing challenges ranging from basic needs to psychosocial well-being, despite who they are and where they come from. Traditional ways of thinking and knowing cannot address these challenges adequately; rather, established divisions of professions, systems, disciplines, and/or areas of practice might just be the factor that constrains the ability to clearly articulate compelling problems and adds an additional layer of complexity to problem solving. This book focuses on country policies and practices, and draws on theoretical ideas that provide the intellectual basis. In addition, it offers vivid examples of how migrant workers manage to work, pursue economic security, strive and adjust in new communities, define and negotiate self and identity, and seek health and well-being. While the book illuminates shared challenges and experiences for each group of migrant workers (i.e. low-skilled workers, internal migrants and other types of migrating laborers), it also synthesises the intersectionality across all migrant workers, as they remain committed to bettering the lives of their families and communities in their origin countries as well as new host countries and communities. This volume reflects the efforts of interdisciplinary research and collaboration
Keywords: dept.swk

Impact of Changes in Criminal-Legal Practices During the COVID-19 Pandemic on the HIV Risk Behaviors of Women Who Use Drugs: Protocol for a Multimethods Qualitative Study - Smoyer, Amy B. (JMIR Research Protocols, 2024)
Background: HIV risk behavior in women who use drugs is related to myriad psychosocial issues, including incarceration. The experience of incarceration elevates women’s HIV risk by disrupting social networks, housing, employment, and access to health care. During the COVID-19 pandemic, changes in criminal-legal practices resulted in decreased incarceration, especially among women. These changes may have largely altered HIV risk among women who use drugs, depending on their access to care in the community. Objective: This study seeks to build knowledge about the impact of shifts in criminal-legal practices during the COVID-19 pandemic on HIV risk behaviors of justice-involved women who use drugs. Methods: Qualitative methods are used to gather and analyze women’s narratives about their life experiences before and during the COVID-19 pandemic, with a focus on individual and structural determinants of HIV risk behaviors. Thirty formerly incarcerated women with a history of substance use are being recruited through collaboration with community partners. Each participant completes a sociodemographic survey and two interviews. The first interview uses a life history instrument that invites participants to reflect on key turning points in their lives. The second interview uses a calendar approach to gather information about participants’ lives during the first year of the COVID-19 pandemic (March 2020-March 2021). The interviews (1 hour each) are audio-recorded and transcribed for analysis. Rapid Qualitative Inquiry and thematic analysis are being used to manage, organize, and interpret the data. The study team will collaborate with a subset of participants to develop digital stories about their COVID-19 experiences, a process that allows for member-checking and triangulation. Findings will be disseminated to program and policy makers in academic venues, community settings, and social service agencies. Results: To date, 10 women’s data have been collected. In total, two themes have been identified in this preliminary data: (1)the chaos and instability of participants’ lives increased during the COVID-19 pandemic: participants reported a wide range of psychosocial and health problems and limited engagement with social service systems. Interaction with criminal-legal systems was rife with uncertainty; participants described living in a state of limbo, which was extremely stressful. (2) When asked to describe a “turning point” in their lives, many participants attributed their substance use to the traumatic loss of a child due to death, incarceration, or termination of parental rights. During the COVID-19 pandemic, participants’ struggles to cope with these unresolved experiences of grief and loss were intensified by the widespread death and dying of the pandemic. Conclusions: Preliminary findings suggest that HIV risk factors increased for participants during the COVID-19 pandemic and invite further investment in community-based harm reduction programs, especially housing, that support women who use drugs. Interventions that address experiences of maternal grief and loss may reduce women’s substance use. Trial Registration:
Keywords: dept.swk; peer-reviewed

Policy Initiatives on Eliminating Anti-Asian Racism - Liu, Meirong; Xu, Yanfeng; Si, Zhanjie (Addressing Anti-Asian Racism with Social Work Advocacy and Action, 2024)
This chapter calls for urgent institutional changes to address structural inequalities through advocacy and legislative action. The authors discuss macro practice methods to address racial injustice through advocacy efforts such as fostering policies eliminating anti-Asian hate and violence, advocating for nondiscriminative policies, improving language access, campaigning for narrative change, building coalitions with social justice groups, encouraging civic engagement, strengthening links with social justice organizations, and promoting policies and programs on Asian American, Native Hawai’ian, and Pacific Islander history education and awareness. Policy advocacy to protect Asian Americans against racial hate crimes is lacking but much needed. Macro social workers’ efforts can pressure policymakers to directly address anti-Asian racism and violence, provide targeted assistance, and call on national, state, and local organizations to ensure investments in culturally appropriate services to Asian American communities.
Keywords: dept.swk

The history of anti-Asian racism and violence in the United States - Liu, Meirong; Lee, Nayoun; Si, Zhanjie; Aquino, Olivia (Addressing Anti-Asian Racism with Social Work Advocacy and Action, 2024)
This chapter begins with a review of the history of anti-Asian racism in the United States. Beginning in the mid-19th century, Asian immigrants played a vital role in the development of the country. However, Asian Americans have faced a long legacy of exclusion and inequality, particularly during periods of economic recession, disease outbreaks, or war throughout US history. Adopting the framework of “othering,” this chapter analyzes the major events in US history related to Asian Americans, such as the Chinese Exclusion Act of 1882, the Immigration Act of 1924, the Japanese internment camps during World War II, and the anti-Asian immigration policies adopted by the Trump administration. Through this, the authors illustrate how historic racism and xenophobia at both individual and institutional levels have operated to marginalize Asian Americans and reproduce inequality, and they demonstrate the common roots of racism that lie in White supremacy.
Keywords: dept.swk

Teaching Note—Antioppressive Pedagogy in Action: The Undergraduate Research Methods Course - Smoyer, A.B.; D’Angelo, K. (Journal of Social Work Education, 2024)
The project of engaging undergraduates in research methods courses is an outstanding challenge for social work educators. Anxiety about the subject is common, for both students and instructors. Further, students’ wariness may reflect historical trauma and their knowledge about the ways in which research has been used to oppress people of color; lesbian, gay, bisexual, transgender, queer or questioning, intersex, asexual or ally, and other sexual and gender minorities communities; and other marginalized populations. This teaching note offers reflections and experiences about developing an undergraduate social work research methods course that uses antioppressive pedagogies to create student-centered learning with experiential team-based activities and ongoing critique about the role of power and privilege in research. Specific teaching resources and strategies are shared. © 2024 Council on Social Work Education.
Keywords: dept.swk

Expanding the notion of personal well-being during covid-19 campus closure in India: results from a mixed-methods study with members of higher education - Yeon, G.; Perumbilly, S.; Elangovan, N.; Awungshi, S.; Varghese, K.J. (Asia Pacific Journal of Educators and Education, 2024)
The COVID-19 pandemic has challenged lives globally in unprecedented ways. While numerous studies have discussed the impact of this pandemic on human lives, this descriptive study examined how this pandemic affected personal well-being (PW) for members of Indian higher education in the early phase of the pandemic in 2020 when there were no vaccines and remedies available. Research participants (n = 551) were faculty members, graduate students, and non-teaching staff in Indian higher education. At the time of data collection, when all campuses were closed, all participants were functioning in their roles in the academic communities via virtual platforms. This descriptive study, based on a mixed-methods research design with concurrent triangulation strategies, collected data from all regions of India. Resulting data identified and discussed the impact of the pandemic on six domains of PW in the life of participants: (a) self-care; (b) professional growth; (c) quality of interrelationship within the family; (d) relationships with significant others outside of the family; (e) process of experiencing/facing and addressing challenges; and, (f) relationship with spirituality/transcendental dimensions. The relevance of the last domain may be unique to Indian participants’ socio-cultural context and ethos. The findings and discussion explain how PW is a composite of all these six domains, and the pandemic expanded the notion of PW for the members of Indian higher education. Further, the findings also provided a general orientation on how educational leadership teams and institutions can enhance at least three specific dimensions of their community members and thus increase the likelihood of improving the quality of their professional and personal life. The findings may also have relevance for academic communities worldwide and inform clinicians working with members of academic communities, educational institutions, and policymakers. © Penerbit Universiti Sains Malaysia, 2024.
Keywords: Teacher leadership; dept.mft; distributed leadership; middle leaders; middle leadership; peer-reviewed; teacher leaders

Is Talking About What’s Wrong Necessarily Right: A Positive Perspective on the Diagnostic Interview - O’Brien, Kyle H.; Schlechter, Alan (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: Adolescent; Child; Child Psychiatry; Emotions; Humans; Interview, Psychological; Mental Disorders; Neurodevelopmental Disorders; dept.rec; dept.swk; peer-reviewed

A model of integrated health care in a poverty-impacted community in New York City: Importance of early detection and addressing potential barriers to intervention implementation - Acri PhD, Mary C.; Bornheimer MS, LCSW,Lindsay A.; O’Brien DHSc, MSW, MSOT, LCSW, OTR/L,Kyle; Sezer MPA, Sara; Little PsyD, LCSW-r, SAP, CCM,Virna; Cleek PhD, Andrew F.; McKay PhD, Mary M. (Social Work in Health Care, 2016)
Disruptive behavior disorders (DBDs) are chronic, impairing, and costly behavioral health conditions that are four times more prevalent among children of color living in impoverished communities as compared to the general population. This disparity is largely due to the increased exposure to stressors related to low socioeconomic status including community violence, unstable housing, under supported schools, substance abuse, and limited support systems. However, despite high rates and greater need, there is a considerably lower rate of mental health service utilization among these youth. Accordingly, the current study aims to describe a unique model of integrated health care for ethnically diverse youth living in a New York City borough. With an emphasis on addressing possible barriers to implementation, integrated models for children have the potential to prevent ongoing mental health problems through early detection and intervention.
Keywords: Child mental health; dept.rec; dept.swk; early detection and treatment; integrated care pathway; peer-reviewed

Parental Mental Health: Addressing the Unmet Needs of Caregivers for Children With Autism Spectrum Disorders - Lushin, Viktor; O’Brien, Kyle H. (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: dept.rec; dept.swk; peer-reviewed

International Dialogue: Our Experience in a Family Therapy Program - Mcdowell, Teresa; Fang, Shi-Ruei; Griggs, Julie; Speirs, Karl; Perumbilly, Sebastian; Kublay, Aliye Ebru (Journal of Systemic Therapies, 2006)
In this paper, we report our experiences as part of an international dialogue group within a U.S. family therapy training program. We describe the dialogue group and share the outcomes of our work together, including our understandings of how global relations, social positions, and personal/cultural characteristics influence our interactions within local contexts. We discuss how participation increased our international awareness and competence, offering two illustrations of how the group helped participants consider family therapy practice and research from a global perspective. Finally, we share the subjective experiences of student group members from the Southern United States, India, Turkey, and South Africa as testimony to the value of cross-national dialogue and to making space for affirming the unique journeys of international learners.
Keywords: dept.mft; peer-reviewed

Viewing the Asian American Experience Through a Culturally Centered Research Lens: Do Scholarship in Family Science and Related Disciplines Fall Short? - Fang, Shi-Ruei Sherry; McDowell, Teresa; Goldfarb, Katia P.; MacDonald, Angella; Perumbilly, Seb; Gonzalez-Kruger, Gloria E. (Marriage & Family Review, 2008)
To better understand and serve Asian-Americans, it is imperative for the family science related fields to take a leadership role in providing in-depth insight into Asian-American families. In this article we report a descriptive analysis of articles published in prominent family-based journals over a 14-year period (1992–2006) relative to their attention to Asian-American families. This study examines the types of research conducted and the knowledge that has been generated about Asian-American families. It also provides a framework for considering future culturally centered research with this population.
Keywords: Asian-Americans; culturally sensitive research approaches; dept.mft; family science; peer-reviewed

Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
Keywords: dept.mft; peer-reviewed

Bridging the gap between spirituality and mental health: the need for trauma-informed ministries within Latino communities - Hernandez, V. (Journal of Religion and Spirituality in Social Work, 2024)
The impact of trauma on mental health has led to the increased development of trauma-informed organizations. Little is known, however, about the benefits of using a trauma-informed care perspective within a faith-based setting, particularly among Latino communities. This article reviews the literature and identifies gaps suggesting the problem of a lack of mental health and trauma-informed awareness among places of worship. The need for developing trauma-informed ministries within places of worship is recommended to assist in promoting the psychological, emotional, and spiritual well-being of congregants and community members within faith-based settings. © 2024 Taylor & Francis.
Keywords: Latino; Mental illness; dept.swk; ministry; peer-reviewed; training; trauma-informed

For White Social Workers: RE/UN/DIScover Heuristic for Dual Awareness in Ongoing Anti-Racist Practice - Keenan, Elizabeth (Advances in Social Work, 2023)
Although many White social workers engage in ongoing anti-racist actions, they may still be complicit in perpetuating and reinforcing racism and White Supremacy Culture. Black, Indigenous, and People of Color (BIPOC) social workers, activists, and scholars have described the numerous ways in which the harmful impacts of White Supremacy Culture appear in the well-intentioned efforts of White people who seek to be anti-racist. White social workers are thus responsible for engaging in intentional ongoing practices to identify, interrupt, and shift their interpersonal oppressive uses of power in their practice. The RE/UN/DIScover heuristic is an iterative, embodied set of three practices for working with one’s experiences of shame and internalized dominance, habitual not-seeing, and in-the-moment activations. Literature theorizing White Supremacy ideology and culture frames the description of the RE/UN/DIScover heuristic. This paper describes several heuristic applications, including prompts for engaging in REcover, UNcover and DIScover practices and two composite examples. These applications illustrate how to use the heuristic practices with dual awareness of self and one’s social work practice in the moment and over time. White social workers are encouraged to learn and use the RE/UN/DIScover heuristic practices to guide their efforts to more fully live into their anti-racist commitments in moments of not-seeing and moments of activation.
Keywords: Heuristic; Power; Social work practice; White social workers; anti-racist; dept.swk; peer-reviewed

Designing and Assessing Programs for Social Work - Tomczak, Stephen Monroe (Management and Leadership in Social Work: A Competency Based Approach, 2020)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

Community Collaboration for Social Workers - Tomczak, Stephen Monroe (Management and Leadership in Social Work: A Competency Based Approach, 2020)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

The roots of social work practice - Tomczak, Stephen Monroe; Cross-Denny, Bronwyn (Health Science Faculty Publications, 2023)
Keywords: dept.swk

Book Review: Refusal to Eat: A Century of Prison Hunger Strikes - Smoyer, Amy B. (Punishment & Society, 2023)
Keywords: book.review; dept.swk

Gender and Identity in Prison - Smoyer, Amy B. (The SAGE Encyclopedia of Criminal Psychology, 2019)
Keywords: dept.swk; gender identity; identity; prisons

Book Review: Mothering and desistance in re-entry - Smoyer, Amy B. (Affilia, 2020)
Keywords: book.review; dept.swk

In the Meantime: RE/UN/DIScover Heuristic for Small-Scale Antioppressive Action within Systems and Organizations - Keenan, Elizabeth King (Social Work, 2023)
The dehumanizing effects of neoliberal, white dominant regulations, laws, policies, and cultural assumptions seep into the everyday practice of social workers in frontline and mid-level positions. Many social workers are learning various antioppressive practices and becoming aware of how microaggressions and other oppressive dynamics can manifest in workplaces but lack models to guide efforts for small-scale action. This article describes how the RE/UN/DIScover heuristic can be used to interrupt and shift oppressive processes during everyday moments of practice within organizations and systems by social workers and their interested colleagues who have some awareness of oppressive and antioppressive dynamics. The RE/UN/DIScover heuristic is an iterative set of three practices: (1) tend to self with compassionate REcover practices; (2) engage in curious, critical reflection to UNcover full understandings of the power dynamics, impacts, and meanings of specific challenges; and (3) DIScover and try out just, humanizing responses with creative courage, individually and with other colleagues. The heuristic uses a dual focus on self and situation with an ad hoc group of other colleagues to raise awareness; cultivate humanizing spaces; and implement antioppressive, relational responses. The article describes the heuristic practices and how to apply the heuristic with two composite practice applications.
Keywords: dept.swk; peer-reviewed

African Americans and the Consequences of Discrimination - Howe, Esther; Hamilton, Julia (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Lookism: Bias Based on Appearance - Howe, Esther (Diversity, Oppression, and Social Functioning: Person-In-Environment Assessment and Intervention, 2010)
Keywords: dept.swk

Editorial: We Can Do Better: Meta-analysis Demonstrates Inequities in Psychotherapy Efficacy for Black Children - Bloch, Michael H.; Finch, Krystal (Journal of the American Academy of Child & Adolescent Psychiatry, 2022)
Keywords: dept.swk

Appropriately Uncomfortable: A Conversation Among Three Colleagues About Structural Oppression Focusing on Racism and the Need for Action - Aguilar, Jemel; Smith, Carmela Fusciello; Tomczak, Stephen Monroe (Reflections: Narratives of Professional Helping, 2021)
In this reflection, three social work colleagues discuss three different perspectives on one statement about racism. We detail our emotionally challenging conversations about racism, microaggressions, and the meaning of social justice in social work to build a different bond and sense of understanding. We delve into how we understand each other, our differing viewpoints on the murders of Black people in American society such as George Floyd, and our perspectives on social workers’ relationships to social justice, racism, and social change in the context of the 2020 turmoil.
Keywords: dept.swk; higher education; oppression; peer-reviewed; racism; social work faculty

Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach - Aguilar, Jemel; Carpenter, Elisabeth Counselman (Cognella Academic Publishing, 2021)
Decolonizing Human Behavior in the Social Environment: A Reader for an Anti-Oppressive Approach challenges the socialization of preservice social workers by examining the complex features of individuals, families, groups, and societies and how they present themselves within the context of the multiple and simultaneous influences on behavior, cognitions, and emotions.This text is divided into three distinct units. Unit I development at the individual level and the influences that shape human behavior, including adverse childhood experiences, identity development through social media, resilience, and chronic illness. Unit II focuses on interpersonal dynamics with articles that explore grief theories, the transgender experience, intergenerational trauma, privilege, and more. Unit III examines structural social systems such as institutional racism, religious-based prejudice, and structural violence.Written to help social work students and professionals begin the process of decolonizing their education and practice, Decolonizing Human Behavior in the Social Environment is an essential and timely reader for courses and programs in social work. It is also an exemplary resource for practitioners at all levels.
Keywords: dept.swk

Promoting food justice and the right to adequate food in social work education - Hall-Faul, M.; D’Angelo, K.A.; Libal, K. (Journal of Human Rights and Social Work, 2024)
Food justice is centered on the principle that food is a basic human right. Despite a mandate to include human rights and social justice content in the social work curriculum, food insecurity and food justice receive scant attention in social work academia. Food insecurity affects a substantial portion of the population, with a disproportionate impact on women and Black, Latinx, and Native American communities. A human rights-based approach to food requires more than access to food; it demands that food also be available, adequate, and culturally acceptable. A right to food framework also calls on policymakers to immediately address disparities in food security, which are prevalent in the USA due to historical and ongoing systemic racism. This paper provides a conceptual understanding of food justice and its historical connections to social work, outlines the requirements of a right to food, and concludes by offering strategies to integrate food justice into the micro, mezzo, and macro social work curriculum. © 2024, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Food insecurity; Food justice; Human rights; Hunger; Right to food; Social work; Social work education; dept.swk; peer-reviewed

Transitional Challenges in Technology Adoption among Academic Communities in Indian Higher Education Institutions - N, Elangovan; Yeon, Guydeuk; PERUMBILLY, SEBASTIAN; AWUNGSHI, SARAH HORMEILA (Journal of International Technology and Information Management, 2021)
Keywords: dept.mft; peer-reviewed

Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed

Teaching Note—Innovating the Curriculum: Bringing History Back Into Social Work Education - Abramovitz, Mimi; Curran, Laura; Harty, Justin S.; Toft, Jessica; Tomczak, Stephen Monroe (Journal of Social Work Education, 2024)
History, the major storehouse of information, informs us about the important relationship between people and society and increases our understanding of basic societal values and institutional arrangements. A recent New York Times op-ed described “The Dangerous Decline of the Historical Profession.” Likewise for historical content in social work education, exacerbated by the 1970s‘ rise of neoliberalism and the profession’s long marginalization of historical research and teaching. The Social Welfare History Group renews its call to bring historical content back into social work education and to correct its deep-seated race, class, gender, and colonizing distortions. To ensure that all social work courses include history, we can revive the value historical knowledge; prepare a cadre of historical researchers and instructors; financially support emerging scholars and develop a pipeline of history-informed faculty to teach the next generation of social workers.
Keywords: dept.swk; peer-reviewed

RE/UN/DIScover Heuristic: Working with Clinical Practice Impingements in Dehumanizing Times - Keenan, Elizabeth King (Clinical Social Work Journal, 2023)
Although clinical social work seeks to center the transformative potential of human relationships, practitioners are experiencing heightened systemic and organizational impingements from the dehumanizing pressures of neoliberalism. Neoliberalism and racism diminish the vitality and transformative potential of human relationships, disproportionately affecting Black, Indigenous and People of Color (BIPOC) communities. Practitioners are also experiencing increased stress and burnout related to increased caseloads and decreased professional autonomy and organizational practitioner support. Holistic, culturally responsive, and anti-oppressive processes seek to counter these oppressive forces but need further development to synthesize antioppressive structural understandings with embodied relational interactions. Practitioners can potentially contribute to efforts that apply critical theories and antioppressive understandings within their practice and workplace. Through an iterative flow of three sets of practices, the RE/UN/DIScover heuristic supports practitioners’ efforts to respond in those challenging everyday moments where oppressive forms of power are imposed and embedded within systemic processes. With themselves and other colleagues, practitioners engage in compassionate REcover practices; use curious, critical reflection to UNcover full understandings of power dynamics, impacts, and meanings; and draw on creative courage to DIScover and enact socially just and humanizing responses. This paper describes how practitioners can use the RE/UN/DIScover heuristic in two common challenging moments of clinical practice: systemic practice impingements and implementing a new training or practice model. The heuristic seeks to support practitioners’ efforts to preserve and expand socially just, relational spaces for themselves and those with whom they work within the context of systemic dehumanizing neoliberal forces.
Keywords: Clinical practice; Heuristic; Neoliberalism; Power; Practice challenges; Window of tolerance; dept.swk; peer-reviewed

Book Review: Invisible Mothers: Unseen Yet Hypervisible After Incarceration by Garcia-Hallett, J. - Smoyer, Amy B. (Affilia, 2023)
Keywords: book.review; dept.swk

“Sports! More than just a game” - Smith, Christina (Connecticut history, 2023)
Keywords: dept.swk

Building or Burning: Critical Reflections on Social and Political Change - Krings, Amy; D’Angelo, Karen; Ivery, Jan M.; Murphy-Nugen, Amy B. (Journal of Policy Practice and Research, 2023)
Keywords: dept.swk; peer-reviewed

Macro-Level Social Work Interventions in Schools: Poverty Simulation Programs as Professional Development Opportunities for K–12 Educators - Curry, Anna Maria T.; Tomczak, Stephen Monroe (Children & Schools, 2023)
Keywords: dept.swk

Preface - Logan, Isabel; Green, Cheryl (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Keywords: dept.nur; dept.swk

911: Stabilization approaches used by police social workers - Logan, Isabel; Madden, Robert; Sallaku, Katherine (Stabilization Approaches That Empower Clients Through Mental Health Crises, 2023)
Police social workers are crucial components of police departments when individuals or communities experience crises. They perform essential tasks, including well-being checks, crisis intervention, de-escalation, mediation, safety planning, referrals to community services, and other preventative measures to stabilize clients in crisis. The chapter will define police social work and give the reader insight into the stabilization approaches used by police social workers to prepare clients for their next level of care. The chapter begins with a brief history of the evolution of police social workers within the context of public policy and their most recent call to action to address mental health crises. The authors utilize a multi-tier approach to highlight stabilization approaches used by police social workers with a focus on empowering individuals, families, and communities to collaborate on solutions. The chapter uses case scenarios drawn from the experiences of police social workers and interns to demonstrate stabilization approaches. A racial equity, culturally responsive, and trauma-informed lens informs the approach to stabilizing client systems in law enforcement settings. © 2023, IGI Global. All rights reserved.
Keywords: dept.swk

The influence of spirituality on professional identity, role performance, and career resilience among nursing home social workers - Rogers, Robin K.; Myers, Dennis R.; Garrison, Brianna V.; Singletary, Jon E.; McClellan, Angela (Journal of Gerontological Social Work, 2023)
This paper explores how social workers integrate personal spirituality within nursing homes, where a highly regulated, stressful environment marginalizes professional identity and challenges retention. Researchers offer new evidence of how spirituality informs professional identity, ethical practice, and continuation in the role. Twenty BSW/MSW licensed nursing home social workers (NHSWs) reported how they daily navigate the personal spirituality-at-work opportunity and challenge. Qualitative analysis of in-depth interviews resulted in three primary codes and related subcodes: Spirituality-Integrated Professional Identity (Vocational Affirmation and Value Alignment), Spirituality-Informed Practice (Intervention Asset, Relational Affinity, and Ambiguous Boundaries), and Spiritually-Sustained Career Resilience. Respondents reported how spirituality animated professional identity, informed daily role enactment, and sustained role involvement. Recommendations are provided for normalizing ethical spirituality-at-work through social work education and practical guidance in navigating the spirituality and practice space.
Keywords: Nursing Home; dept.swk; peer-reviewed; spirituality

Origins of Social Group Work; Special Issue of Social Work With Groups, Volume 46, Issue 4. - Gardella, Lorrie Greenhouse (Taylor and Francis, 2023)
Keywords: dept.swk

Stabilization approaches that empower clients through mental health crises - Logan, Isabel; Green, Cheryl A. (IGI Global, 2023)
Mental health practitioners often overlook initial stabilization strategies and interventions when providing evidence-informed approaches in order to get to the so-called “important” or “interesting” part of treatment. For many mental health practitioners, the “important” or “interesting” component...
Keywords: dept.nur; dept.swk

Bilingual Court Professionals’ Perceptions of Their Language Skills: Asset or Liability? - Logan, Isabel; Negroni, Lirio K. (Advances in Social Work, 2021)
Bilingual professionals are considered an asset in the workplace. However, bilingual professionals at times perceive their language skills as a liability. This paper examined bilingual professionals’ perceptions of their language skills and the factors that influence their views. Focus groups were used to capture the perspectives of 15 bilingual professionals who speak English and Spanish and work in a court system in the eastern region of the United States. Findings reveal challenges rooted in discrimination that convert bilingual professionals’ perceptions of their language skills from an asset to a liability. Participants highlight unfair practices affecting Limited English Proficiency (LEP) clients. These practices force bilingual professionals to become protectors and gatekeepers to prevent adverse outcomes and provide access to services in the court and across social service systems. Ultimately, bilingual professionals’ perceptions of their language skills depended on how others used their language skills in the workplace. To support bilingual professionals and provide quality services to LEP clients, social work administrators must evaluate structural supports and provide training specific to the cultural aspect of language for all employees.
Keywords: Bilingual Professionals; Court system; Discrimination; Language; Social Work; dept.swk; peer-reviewed

Isn’t that why you were hired? - Logan, Isabel (Journal of Ethnic & Cultural Diversity in Social Work, 2018)
Human service organizations seek bilingual professionals to meet the social and linguistic needs of their increasingly limited English proficient (LEP) clientele. As a result, bilingual professionals often find themselves having to meet overwhelming service delivery expectations. This paper reports on a qualitative study about the work experiences of 27 court employees within a judicial system in the Eastern United States. The study found that bilingual professionals encounter challenges because of their language skills. At the intersection of these challenges are microaggressions that manifest in the judicial system, adversely affecting them professionally and personally.
Keywords: Bilingual professionals; criminal/juvenile justice; dept.swk; judicial system; microaggressions; peer-reviewed; social work education and training

Snow Day - Gardella, Lorrie Greenhouse (Washing Lines of the World, 2023)
Keywords: dept.swk

Preparing social workers for emerging roles in police social work - Logan, Isabel; Madden, Robert; Solak, Matthew (Journal of Social Work Education, 2023)
Schools of social work must prepare social workers to meet the demands of the rapidly emerging field of police social work. This article reports on the experiences of a social work program’s partnership with a police department. The authors identify an integrative practice model of police social work, specifying social work roles at the baccalaureate and graduate levels, as well as ethical issues. The model is based on the social work competencies and law enforcement best practices. The authors analyze the experiences of placing students directly into law enforcement settings and make recommendations to create successful experiences for students, social workers, and police. The importance of strategic partnerships, communication, trust, and support in building strong relationships is also highlighted.
Keywords: dept.swk; peer-reviewed

Leading in color in academia: a latinx chair’s experience of resiliency and hope - Reyes, Loida (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
On Wednesday, January 20, 2021, Kamala Harris broke through the gender and racial barrier that has kept men at the top ranks of American politics for over two centuries. This moment singlehandedly challenged the definition of leadership and who “fits” in that traditional model. Reyes examines the challenges and highlights three lessons of leading in color in academia today, being the first Latina to chair her department. Her journey reflects similar experiences of women of color who are burdened by the emotional toll that comes with being a part of systemic change, by virtue of leading while of color. To begin dismantling systemic racism and sexism, organizations must commit to addressing the issues head-on by reexamining policies, practices, and work environments that have perpetuated systemic inequalities. Greater supports are needed for women of color to be effective as their contributions are invaluable in achieving true systemic change.
Keywords: Academia; Hope; Latinx experiences; Resiliency; dept.swk

Trusted residents and housing assistance to decrease violence exposure in New Haven (TRUE HAVEN): a strengths-based and community-driven stepped-wedge intervention to reduce gun violence - Tong, Guangyu; Spell, Virginia T.; Horton, Nadine; Thornhill, Thomas; Keene, Danya; Montgomery, Christine; Spiegelman, Donna; Wang, Emily A.; Roy, Brita (BMC Public Health, 2023)
We describe the rationale and study design for “TRUsted rEsidents and Housing Assistance to decrease Violence Exposure in New Haven (TRUE HAVEN),” a prospective type 1 hybrid effectiveness/implementation study of a multi-level intervention using a stepped wedge design. TRUE HAVEN aims to lower rates of community gun violence by fostering the stability, wealth, and well-being of individuals and families directly impacted by incarceration through the provision of stable housing and by breaking the cycle of trauma.
Keywords: Collective wellbeing; Community-based intervention; Gun violence; Housing stability; Incarcerated population; Learn as you go; Multi-component implementation; Stepped wedge design; Structural racism; dept.swk; peer-reviewed

Group well-child care as a facilitator of psychoeducation: pediatrics residents’ perspectives - Nogelo, Patricia Faraone; Oldfield, Benjamin J; Fenick, Ada M; Rosenthal, Marjorie S (Health Education Research, 2023)
Psychoeducation, where clinicians teach problem-solving skills in a supportive environment, can help address families’ social vulnerabilities and promote well-being. Group well-child care (GWCC) may provide unique opportunities for pediatric residents to improve their skills in psychoeducation. Our aim was to characterize pediatric residents’ perspectives and experiences of communication while conducting both individual well-child care and GWCC. We used a longitudinal qualitative study design to conduct 15 semistructured interviews with five pediatric residents who facilitated GWCC. Using the constant comparative method, we characterized pediatric residents’ perspectives and experiences of communication while conducting both individual well-child care and GWCC. Four themes emerged. Residents perceived that GWCC (i) enabled families to honestly share their knowledge and parenting practices, (ii) allowed time and a space for families to share personal stories and scenarios, (iii) facilitated discussions of maternal health and psychosocial matters, toward which residents felt ambivalence, and (iv) fostered skills in psychoeducation that transferred to the rest of their clinical practice. When pediatric residents lead GWCC, they perceive that they can facilitate key aspects of psychoeducation, enabling them to assist families in meeting complex social needs. Residents describe that they transfer psychoeducation skills learned in GWCC to the rest of their practice.
Keywords: dept.swk; peer-reviewed

Sabbatical Leave Report: Sabbatical Spring, 2015 - Keenan, Elizabeth King (Distribution: Spring ; Social Work., 2015)
From the report: "Project title: Walking the walk or just talking the talk? An exploratory study of the ways social workers understand social work practice." The report describes the research problem, identifies three reserach questions, and discusses the project outcomes and reporting.
Keywords: dept.swk; faculty_collection; sabbatical_report

Managing War Trama in Veterans and Their Families. - Dripchak, Valerie L. (2011)
Keywords: dept.swk; faculty_collection; sabbatical_report

Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

Early Detection of Schizophrenia: Phenomenological Markers. - Rakfeldt, Jaak (2000)
Keywords: dept.swk; faculty_collection; sabbatical_report

Louis Lowy: Lehren aus dem Holocaust - Sozialarbeit unter extremen Bedingungen - Gardella, Lorrie Greenhouse (Lambertus-Verlag, 2019)
Keywords: Biography; Biography; Jewish refugees; Biography; Jews; Biography; Jews, Czech; Biography; Social workers; Boston; Czech Republic; Deggendorf; Germany; Lowy, Louis; Holocaust survivors; Massachusetts; Prague; United States; dept.swk; faculty_collection

Group Work: Creating Space for All Voices - International Association for Social Work with Groups International Symposium Chapel Hill, North Carolina); Gardella, Lorrie Greenhouse; Tully, Greg (Whiting & Birch Ltd., 2019)
Keywords: Congresses; Social group work; dept.swk

Walking the Walk or Just Talking the Talk?: An Exploratory Study of the Ways Social Workers Understand Social Work Practice - Keenan, Elizabeth King (2015)
Keywords: dept.swk; faculty_collection

The Common Factors Model for Generalist Practice - Cameron, Mark; Keenan, Elizabeth King (Pearson Education, 2013)
Keywords: Social work administration; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Pearson/Allyn and Bacon, 2011)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Responding to the Oppression of Addiction: Canadian Social Work Perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2010)
"Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community."--pub. desc.
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; faculty_collection; therapy; Social Work; Canada

The Roots of the Recovery Movement in Psychiatry: Lessons Learned - Davidson, Larry (Wiley-Blackwell, 2010)
Keywords: History; Social psychiatry; Community psychiatry; Humanistic psychotherapy; Recovery movement; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A. (Pearson/Allyn and Bacon, 2007)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

A Dream and a Plan: A Woman's Path to Leadership in Human Services - Gardella, Lorrie Greenhouse; Haynes, Karen S.; National Association of Social Workers (NASW Press, 2004)
Keywords: Administration; Leadership; Promotions; United States; United States; Career development; United States; Human services; United States; Women executives; United States; Women social workers; Women social workers; dept.swk; faculty_collection

Working-Class Gay and Bisexual Men - Appleby, George A. (Harrington Park Press, 2001)
Keywords: Services for; Services for; Bisexual men; Social work with gays; Gays; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Allyn and Bacon, 2001)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Negotiating toilet access: a qualitative exploration of women's incarceration - Smoyer, Amy B.; Schwarz, Paige; Camenga, Deepa; Rickey, Leslie (The Prison Journal, 2023)
Norms and behaviors about toileting in prison can expand understanding of women's lived experience of incarceration. Knowledge about this subject is significant because access to clean, safe toilets is a human rights issue, and toilet habits can impact social, mental, and physical outcomes. Three focus groups were conducted with 15 incarcerated women about their quotidian prison toilet experiences. While the toilet was physically available, institutional regulations, social norms, and women's individual psychologies limited their access and utilization. The ways in which toilet use was negotiated with self, peers, and are described, and the implications of these findings are discussed.
Keywords: dept.swk; peer-reviewed

Addressing America's Mental Health Crisis in Public Education - Albee, Laura Jane (Perspectives and Considerations on Navigating the Mental Healthcare System, 2023)
Nearly eight million American youth between the ages of 3 - 17 live with a psychiatric or behavioral health disorder. Many in grades K-12 are being unfavorably impacted in the classroom because of socioeconomic and environmental factors that include poverty, addiction, incarceration, trauma, domesti...
Keywords: dept.swk; peer-reviewed

Capstone Handbook - Rofuth, Todd W.; Piepenbring, Julie (2022)
Capstone Handbook has been produced as a practical guide for students in the final year of their MSW program. It is intentionally designed to provide brief overviews of the lock-step approach to completing a capstone or thesis project and includes activities to help partialize the steps that will culminate in the completion of the capstone. It contains 30 chapters spanning two semesters with each chapter providing chapter objectives, an introduction, chapter content, a summary of the chapter, end of chapter exercises, references and ancillary material. An overview of all key concepts required in a typical capstone provides students with a practical resource to guide them through the process of creating capstone proposals and final products. Lastly, the eBook’s intent is to afford students with some structure for getting starting by providing a number of templates.
Keywords: dept.swk

Humans peeing: Justice-involved women’s access to toilets in public spaces - Smoyer, Amy B.; Pittman, Adam; Borzillo, Peter (PLOS ONE, 2023)
Justice-involved women face myriad challenges as they negotiate the terms of community supervision and manage the long-term implications and stigma of living with a criminal record. Major tasks that women juggle include securing safe, affordable housing, finding and retaining employment, accessing physical and mental health care (including substance use treatment), and handling relationships with family, friends, children, and intimate partners. In addition to these responsibilities, women must meet their basic physiological needs to eat, sleep, and use the toilet. Women’s ability to safely meet their personal care needs may impact their capacity to manage their criminal-legal challenges. This study uses qualitative methods to understand justice-involved women’s lived experiences related to urination. Specifically, the study reports on a thematic analysis of 8 focus groups conducted with justice-involved women (n = 58) and the results of a toilet audit conducted in the downtown areas of the small city in the United States where the focus group participants were living. Findings suggest that women had limited access to restrooms and reported urinating outside. Lack of restroom access impacted their engagement with social services support and employment and their ability to travel through public spaces. Women perceived their public toilet options as unsafe, increasing their sense of vulnerability and reinforcing the idea that they did not have full access to citizenship in the community because of their criminal-legal involvement. The exclusion and denial of women’s humanity that is perpetuated by a lack of public toilet access impacts women’s psychosocial outcomes. City governments, social service agencies, and employers are encouraged to consider how lack of toilet access may impact their public safety and criminal-legal objectives and expand opportunities for people to access safe restroom facilities.
Keywords: Bladder; Employment; Jobs; Mental health and psychiatry; Prisons; Sexual and gender issues; Urban areas; Urination; dept.swk; peer-reviewed

Collaborating with transgender youth to educate healthcare trainees and professionals: randomized controlled trial of a didactic enhanced by brief videos - Martin, Andrés; Celentano, Jillian; Olezeski, Christy; Halloran, Justin; Penque, Brent; Aguilar, Jemel; Amsalem, Doron (BMC Public Health, 2022)
In collaboration with members of the transgender and gender diverse (TGD) community, we created a didactic resource about the unique needs of TGD youth.
Keywords: Adolescents; Gender-diverse; Health; Health education; Mental health; Transgender; dept.mft; dept.swk; peer-reviewed

Origins of social group work: local stories from around the world - Gardella, Lorrie Greenhouse (Social Work With Groups, 2023)
Keywords: dept.swk; peer-reviewed

If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
Keywords: White supremacy; dept.swk; peer-reviewed

Incarcerated People Living with HIV: A Qualitative Exploration of Stigma - Smoyer, Amy B; Ferris, Shannon; Earnshaw, Valerie A (Health & Social Work, 2022)
Thousands of people living with HIV are incarcerated in the United States. Research about this vulnerable community has focused on access and adherence to medical care, including the impact of stigma on these treatment outcomes. This study presents qualitative data collected from 18 incarcerated and formerly incarcerated men and women living with HIV to expand knowledge about how HIV stigma shapes the lived experience of incarceration. The HIV Stigma Framework, including theory about enacted, anticipated, and internalized stigma, was used to analyze participants’ narratives. Findings demonstrate an ongoing struggle with all three of these stigma mechanisms. Most participants deliberately concealed their HIV status and, therefore, experienced little enacted stigma. However, their narratives do describe anticipated stigma and, to a lesser extent, internalized stigma. There were gender differences in HIV disclosure and symbolic stigma and intersectionality are used to understand this variation. These findings illustrate the persistence of HIV stigma in correctional institutions and underscore the importance of fighting HIV stigma and homophobia within social work practice.
Keywords: dept.swk

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found

Stress, Marginalization, and Disruption: A Qualitative Rapid Situational Assessment of Substance Users and HIV Risk in Lebanon - Khoshnood, Kaveh; Smoyer, Amy B.; Maviglia, Francesca; Kara, Janine; Khouri, Danielle; Fouad, Fouad M.; Heimer, Robert (International Journal of Environmental Research and Public Health, 2022)
Lebanon is a diverse and dynamic nation of six million people that has experienced considerable disruption for the last two decades. The Syrian Civil War, which began in 2011, resulted in the displacement of 1.1 million Syrians to Lebanon. Today, Lebanon is the country with the largest per capita number of refugees in the world. In addition, the country experienced a social, economic, and political crisis in 2019 that destabilized the entire society-circumstances that were further complicated by COVID-19 pandemic. With all of the competing calamities in Lebanon, there has been limited scientific investigation into substance use and the risk of HIV infection among the country's population. To address this gap in knowledge, a qualitative rapid situational assessment (RSA) of substance use and risk of HIV infection in and around Beirut, the nation's capital, was conducted. The goal of this analysis is to describe the demographics and drug use patterns of this population, explore their HIV knowledge and risks, and build knowledge about their perceptions of and access to substance use treatment and other social services.
Keywords: COVID-19; Drug Users; HIV Infections; HIV risk; Health Services Accessibility; Humans; Lebanon; Pandemics; Refugees; Stress, Psychological; Substance-Related Disorders; dept.swk; peer-reviewed; rapid situational assessment; refugees; substance use

The Origin and Evolution of the Term “Social Work” - Luquet, W.; Tomczak, S.M. (Journal of Sociology and Social Welfare, 2022)
The origin of the term “social work” has long been misattributed to the 1907 work of economist Simon Patten. While Patten’s contribution to social work is important, though mostly forgotten, the term had been used long before regarding the work of nuns and settlement workers. Quoting archival and historical findings, this article traces the origin, evolution, and widespread use of the term “social work.” The words of the early founders of social work are utilized to tell the story of how the work of persons doing “the social work” of the church or settlement evolved into the name of the profession. These shifts in terminology in social work’s early history have influenced the subsequent direction of the field up to the present day. © 2022, Western Michigan University. All rights reserved.
Keywords: Simon Patten; dept.swk; history; peer-reviewed; profession; settlements; social work; ⛔ No DOI found

The Impact of Spirituality and Religious Practice on Senior Living Leader Career Resilience - Myers, Dennis R.; Rogers, Robin K.; Garrison, Brianna V.; Singletary, Jon E.; Groce, Haley (Journal of Applied Gerontology, 2022)
Experienced senior living leaders (SLLs) report the impact of spirituality and religious practice on SLL role adaptation and continuation. The sample included 18 SLLs in 18 skilled care settings representing public, non-profit, and for-profit types of incorporation, with oversampling of for-profit facilities. The average years of SLL experience was 24 years. In-depth interviews were examined through a thematic analysis approach using Excel software. Seventy-eight percent described how a higher power, religious beliefs, and faith practices were associated with their role. Their narratives revealed three major themes: Frame (calling and pre-dispositional spiritual beliefs and religious practices), Role Performance (how spirituality informed SLL administrative practice), and Benefits (perceived rewards of adherence to spiritual beliefs and practices). Further analysis of the three themes produced codes that added greater specification for each theme. Implications provided for normalizing the spirituality and work-life intersect and infusing ethical integration of spirituality and work-life in SLL educational programs.
Keywords: adminstration; career resilience; dept.swk; faith and work; peer-reviewed; religious practices; skilled care; spirituality

The ins and outs of posttraumatic growth in children and adolescents: A systematic review of factors that matter - Ferris, Cheyenne; O'Brien, Kyle (Journal of Traumatic Stress, 2022)
Posttraumatic growth (PTG) refers to a positive psychological change that occurs following a seismic and highly challenging life circumstance. An individual who experiences PTG reports posttrauma development that surpasses their baseline level of pretrauma function in various domains. The present systematic review of the current literature aimed to explore factors related to the development of PTG in children and adolescents exposed to trauma. Included studies investigated a range of factors that impact PTG development in youth from five countries: the United States, Israel, China, Japan, and Norway. Studies addressed multiple types of traumatic experiences, including medical trauma, war- and terror-related trauma, and environmental trauma. Findings suggested that factors that impact the development of PTG include the presence of posttraumatic stress symptoms, specifically intrusiveness, and cognitive factors, such as the use of positive reappraisal and deliberate rumination. Many factors demonstrated inconsistencies across studies, such as the impact of age, gender, social support, and parent factors. The findings from this systematic research study encourage the notion that certain clinical intervention strategies, such as deliberate rumination, positive reappraisal coping strategies, and trauma-informed group therapy, may facilitate growth in trauma survivors. Future research should test if these intervention strategies directly impact growth and whether there is an evidence-based form of intervention that can assist clinicians in taking a growth- and strengths-based perspective after trauma.
Keywords: dept.swk; peer-reviewed

Introduction - Flynn, D.S.; Siegel, E. (Gerontology and Geriatrics Education, 2001)
Keywords: dept.swk

The supervisor in aging services - Corley, C.S.; Takamura, J.; Siegel, E. (Supervision as Collaboration in the Human Services: Building a Learning Culture, 2004)
Keywords: dept.swk

The impact of terrorism, terror and trauma on children: Implications for treatment - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2004)
Keywords: alcohol; antidepressant agent; article; battle injury; behavior therapy; beta adrenergic receptor blocking agent; case report; child; child behavior; cognitive therapy; cultural factor; cyproheptadine; dept.swk; family violence; fear; female; fluoxetine; human; imipramine; immune system; male; nightmare; paroxetine; play therapy; posttraumatic stress disorder; propranolol; psychotrauma; self medication; serotonin uptake inhibitor; sertraline; sexual abuse; street drug; terrorism; tricyclic antidepressant agent; ⛔ No DOI found

Managing school discipline and implications for school social workers: A review of the literature - Cameron, M. (Children and Schools, 2006)
School disciplinary policies and practices are essential features of life in U.S. schools. Conventional approaches to school discipline - including conduct codes and security methods, suspension, corporal punishment, and teachers' methods of managing student behaviors - rely primarily on deterrence, control, and punishment to maintain order. However, approximately 40 years of research, chiefly in education and psychology, has demonstrated that these policies and practices are often associated with and can contribute to increased disorder in schools and behavioral and academic problems among students. Furthermore, school discipline is sometimes administered prejudicially to those students who may be the most vulnerable. School social workers and all social workers working with children and youths can help schools adopt effective and nonpunitive disciplinary approaches. Key professional actions include advocacy for schoolchildren subject to unfair and overly punitive discipline; educating teachers and administrators about the potential harm associated with conventional disciplinary practices; educating school personnel about effective, nonpunitive approaches; and creating a public campaign to generate popular support for the reform of iatrogenic school disciplinary practices. © 2006 National Association of Social Workers.
Keywords: Children; Discipline; Punishment; School social work; Schools; dept.swk

School discipline and social work practice: Application of research and theory to intervention - Cameron, M.; Sheppard, S.M. (Children and Schools, 2006)
Research has identified a relationship between school disciplinary actions and poor academic and psychosocial functioning of students subjected to them. The ways in which school discipline is a direct contributor to students' academic and psychosocial difficulty needs to be further established empirically. Several theories, based in existing research and theory in sociology of education and educational psychology, have been proposed to explain the school discipline - student dysfunction relationship. They generally suggest three pathways: disciplinary actions may contribute to students' psychological problems; student misbehavior may be encouraged through ineffective and unintentionally paradoxical learning experiences; and disciplinary practices may damage students' relationship with school. School social workers and others working with children who have been disciplined at school can use these research findings and theories as an assessment framework to guide their interventions.The awareness of the iatrogenic potential of school discipline and informed assessment can support a range of evidence-based alternatives to school discipline. © 2006 National Association of Social Workers.
Keywords: Assessment; Children; Discipline; School social work; Schools; dept.swk

Social work practice with LGBT people within organizations - Appleby, G.A.; Colon, E. (Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed., 2008)
Keywords: dept.swk

Bullying - Howe, E.; Haymes, E.; Tenor, T. (The School Practitioner's Concise Companion to Preventing Violence and Conflict, 2010)
This chapter reviews the most well-researched, evidence-based antibullying interventions: involvement of all the stakeholders in a school, prevention through life skills curricula, problem-solving approaches, and those that focus on rules and consequences. Two factors emerge with clarity: (1) the exact components of the program do not matter as much as the quality and thoroughness with which the interventions are implemented; and (2) given the potentially severe consequences of bullying, it is a moral imperative to continue to implement such programs and to formulate and revise the programs based on solid evidence. © 2008 by Oxford University Press, Inc. All rights reserved.
Keywords: Anti-bullying; Bullies; Bullying; School policy; School safety; School violence; School-based intervention; dept.swk

The importance of housing, neighborhood and community contexts - Allison, K.W.; Broce, R.S.; Houston, A.J. (Adolescent Development and School Achievement in Urban Communities: Resil. in the Neighborhood, 2012)
Keywords: dept.swk

Social work practice with gay men and lesbians within organizations - Appleby, G.A. (Foundations of Social Work Practice with Lesbian and Gay Persons, 2013)
The premise ofthis chapter is that U.S. society will reject continued attempts to defend discrimination against lesbian and gay people in the name of “family values? or “special rights? or “preservation ofmorale? or any other meaningless slogan. Such discrimination will be seen for what it really is: bigotry. However, social change is slow and discriminatory attitudes and behaviors will continue to be oppressive environmental and organizational influences on lesbian and gay social workers employed by human service agencies. This vestige of homophobia and heterosexism, therefore, must become the target of social work intervention (Appleby, 1995). © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

Alcohol Use Among Latino Males: Implications for the Development of Culturally Competent Prevention and Treatment Services - Colon, E. (Alcohol Use/Abuse among Latinos : Issues and Examples of Culturally Competent Services, 2014)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature. © 1998 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

Evolving from an illusionary and self destructive quest for power to a state of empowerment: The curative potential yoga may hold as a vehicle to reclaiming bodily empowerment for women with anorexia - Pizzanello, H.C. (Journal of Sociology and Social Welfare, 2016)
Eating disorders disproportionately afflict women and they are one of the most lethal mental health conditions that practitioners in the field of social work and related mental health fields encounter. Equally alarming is the fact that Anorexia Nervosa is the deadliest of all eating disorders, yet, we are struggling to find an efficacious means of successfully intervening in the treatment and recovery maintenance of anorexia. Drawing from past empirical and theoretical literature, this study explored the potential that the mind body practice of yoga might hold as a complementary therapeutic tool for women struggling to recover from anorexia. The findings that emerged from the analysis of this study’s data indicate that yoga can play a curative role with this population. The findings also revealed that yoga’s primary efficacy resides in its potential to facilitate an experience of connected acceptance and feelings of empowerment in this population of women. © 2016, Western Michigan University. All rights reserved.
Keywords: Anorexia; Feminism; Therapeutic intervention; Yoga; dept.swk; ⛔ No DOI found

Organizational practice with LGBT people - Colon, E. (Social Work Practice with Lesbian, Gay, Bisexual, and Transgender People, 2017)
Keywords: dept.swk

Developing a financial literacy program with survivors of intimate partner violence: The voices of survivors - Stylianou, A.M.; Counselman-Carpenter, E.; Redcay, A. (Social Work (United States), 2019)
As the social work field increasingly recognizes economic abuse within intimate partner relationships, the field has developed financial empowerment programs to empower survivors for their financial future. Although research has demonstrated the effectiveness of financial literacy programs, there are barriers to their implementation in the field. Studies have explored, from the perspective of advocates, best practices in incorporating financial literacy into services; however, no studies have explored implementation approaches from the perspective of survivors. This study explores, from the perspective of 34 survivors, approaches for implementing financial literacy programming. Participants described their understanding of financial empowerment as being in charge of finances, having financial power, and not having to endure the struggle. To counter financial disempowerment, participants identified the need for financial confidence, knowledge, and tools. Participants shared their strategies for saving money, though many participants reported barriers to using banks as savings tools. Almost all participants stressed the importance of financial literacy services for survivors, especially around banking, credit, and debt. Finally, participants shared recommendations for job readiness and training programming. Findings have implications for domestic violence and broader social work organizations implementing financial empowerment services. Social workers can support financial empowerment efforts through program development and research efforts. © 2019 National Association of Social Workers.
Keywords: Adult; Crisis and trauma; Female; Financing, Personal; Humans; Intimate Partner Violence; Literacy; Male; Power, Psychological; Program Evaluation; Qualitative methods; Service delivery; Social Work; Social work practice; Survivors; adult; dept.swk; female; financial management; human; literacy; male; partner violence; peer-reviewed; procedures; program evaluation; psychology; social work; survivor

Effect of a brief social contact video on transphobia and depression-related stigma among adolescents: A randomized clinical trial - Amsalem, D.; Halloran, J.; Penque, B.; Celentano, J.; Martin, A. (JAMA Network Open, 2022)
Importance: Transphobia and stigma remain barriers to seeking mental health care for gender-diverse adolescents. Objective: To examine the utility of brief social contact-based video interventions of transgender protagonists with depression to reduce transphobia and depression-related stigma and increase treatment-seeking intentions among adolescents in the general population. Design, Setting, and Participants: During August 2021, a total of 1437 participants were recruited and randomly assigned to 1 of 4 video-based conditions in a 2:2:1:1 ratio: (1) transgender adolescent girls, (2) transgender adolescent boys, (3) cisgender adolescent girls, or (4) cisgender adolescent boys. Interventions: In each of the approximately 110-second videos, an empowered presenter shared their personal story about coping with depression and reaching out for help. Main Outcomes and Measures: The primary outcome was the score on the Attitudes Toward Transgender Men and Women (ATTMW) scale. Secondary outcomes were (1) a "gender thermometer" rating for warmth in transgender perception, (2) the Depression Stigma Scale (DSS) score, and (3) the General Health-Seeking Questionnaire (GHSQ) score. Results: Of the 1437 randomized participants, 1098 (76%) completed the postintervention assessment and passed all the validity tests (mean [SD] age, 16.9 [1.2] years; 481 [44%] male; 640 [58%] White). A significant change in attitudes toward transgender youth was found within the intervention group only (mean [SD] ATTMW scores: intervention group, 34.6 [23.1] at baseline to 32.8 [24.2] after intervention; P ¡.001; control group, 33.5 [23.4] at baseline to 32.4 [24.1] after intervention; P =.01). The mean (SD) total DSS scores decreased significantly across study groups (intervention: 1.3 [3.3]; control: 1.7 [3.3]; P ¡.001). A significant increase in intention to seek help from a parent was found in the intervention (mean [SD] GHSQ score, 0.2 [1.1]) and control (mean [SD] GHSQ score, 0.3 [1.2]) groups (P ¡.001), as was a decrease in those not wanting to seek help from anyone (mean [SD] GHSQ score: intervention, 0.2 [1.6], P =.009; control, 0.3 [1.2], P ¡.001) Secondary analyses revealed significant differences in baseline ATTMW scores and intervention effects between transgender and gender-diverse and cisgender participants and between lesbian, gay, bisexual, or queer (LGBQ) and straight participants (F = 36.7, P ¡.001) and heterosexual participants (F = 37.0, P ¡.001). A significant difference was also found in mean (SD) transgender warmth scores from baseline to after intervention between groups (2.6° [13.1°] in the intervention group vs 0.4° [8.3°] in the control group; P ¡.001). Conclusions and Relevance: In this randomized clinical trial, brief social contact-based videos proved efficacious in reducing transphobia and depression-related stigma and in increasing treatment-seeking intentions among adolescents in the general population. By personifying, individualizing, and providing face and voice to the experience of transgender youth, other adolescents, especially those who are cisgender and/or of a heterosexual orientation, can gain empathetic insights into the lives of their often marginalized and stigmatized fellow youth. Trial Registration: ClinicalTrials.gov Identifier: NCT04969003. © 2022 Collabra: Psychology. All rights reserved.
Keywords: Adolescent; Depression; Female; Humans; Male; Patient Acceptance of Health Care; Prejudice; Social Stigma; Transgender Persons; Video Recording; adolescent; controlled study; depression; dept.mft; dept.swk; female; human; male; patient attitude; peer-reviewed; prejudice; psychology; randomized controlled trial; social stigma; transgender; videorecording

Book Review: Free Cyntoia: My search for redemption in the American prison system: - Smoyer, Amy B. (Affilia, 2021)
Keywords: book.review; dept.swk; peer-reviewed

Best practices for assessing digital literacy and strengthening online teaching pedagogy of digitally immigrant stakeholders in higher education - Counselman-Carpenter, Elisabeth; Aguilar, Jemel P. (Springer International Publishing, 2021)
Keywords: dept.swk

‘The mirage of action’: Exploring the social work professions’ perpetuation of white supremacy through ‘Well-Intentioned’ actions - Aguilar, Jemel P.; Counselman-Carpenter, Elisabeth (Advances in Social Work, 2021)
This autoethnographic study highlights complex strategies for maintaining white supremacy used by “well-intentioned” heterocentric white female social workers that are enacted under the guise of practicing anti-racism in social work practice settings, classroom environments, policy initiatives, and advocacy work. Using autoethnography was both unplanned and deliberate. Unplanned, we needed a research method that allows us to explore the untouchable subject of heterocentric white female social workers and deliberate in that we could use our experiences to break ground and establish white supremacy among heterocentric white female social workers that espouse anti-racist values as an area of study. We draw on education, anthropology, sociology, and other disciplines to name some of the ongoing challenges to dismantling racism, colonialist, and reformer narratives in social work, and identify strategies used by all white folx, but particularly heterocentric white female social workers to neutralize the suggestion or accusation of their acts as racism. We name three challenges to dismantling racism among heterocentric white female social workers: hiding behind the data, anti-racist book clubs, and crying and comfort. We conclude with further questions for those who hold power in the field and a reflection upon our own continued intersecting struggles with these concepts. © 2021 Authors,.
Keywords: dept.swk; peer-reviewed

Deepening the learning: Intersectional experiential activities to address white supremacy - Keenan, Elizabeth King; Kozu, Shuei; Mayhew, Hunter; Saiter-Meyers, Evelyn; Meggett, Caliyah; Reynolds, Paige (Advances in Social Work, 2021)
Graduate students of multiple racial identities in predominantly White institutions enter social work programs with a wide range of knowledge about and experiences of White Supremacy, particularly the ways in which structural forms of racism continue to inflict harm, block opportunities, and perpetuate wealth inequities. In addition, White students are often challenged to grasp the ways they have been socialized to participate in perpetuating White Supremacy. This wide range of knowledge and experiences makes it likely that students will experience a range of emotions and defensive resistance necessitating skillful pedagogical design and facilitation of class interactions. Intentional use of theoretical frameworks with experiential activities can deepen self-awareness and understanding of the systemic nature of White Supremacy (Okun, 2010). In this manuscript, four students and two instructors discuss their learning experiences within a course addressing White Supremacy for students of multiple racial identities in a predominantly White institution. Post-course dialogue amongst these multiracial authors identified six core areas of learning when examining intrapersonal, interpersonal, and structural racism, cultural wealth of BIPOC peoples, and anti-racism actions. Two primary implications for education are: Weave conceptual frameworks with interpersonal experiential activities throughout the course design, and attend to interactional power dynamics during class meetings. © 2021 Authors, Vol. 21 No. 2/3 (Summer 2021), 821-840,.
Keywords: dept.swk; peer-reviewed

Healthcare-induced trauma in correctional facilities: a qualitative exploration. - Elumn, Johanna; Keating, Layne; Smoyer, Amy B.; Wang, Emily A. (Health & justice, 2021)
Background: While incarcerated people are known to experience trauma at higher rates than the general population, little is known about how the correctional health system contributes to trauma rates. Methods: We conducted 20 semi-structured qualitative interviews with men who were recently released from a correctional system to understand their experiences with healthcare systems and medical staff during incarceration. Using reflexive thematic analysis within a critical realist framework, we coded and analyzed the data iteratively to refine and unify emerging themes. Results: The unanticipated concept of healthcare-induced trauma emerged and was revealed in three overall themes: (1) healthcare leading to fear of serious illness or death, (2) healthcare leading to fear of people, including healthcare providers, correctional staff, and other incarcerated people, and (3) the correctional institutional, social, and physical environment leads to fear of place. Conclusions: Healthcare in correctional settings has the potential to induce trauma, even when the medical conditions addressed are not life-threatening. Future research should examine the factors contributing to the development of healthcare-induced trauma in correctional settings and develop interventions to prevent and address this phenomenon. © 2021, The Author(s).
Keywords: dept.swk; peer-reviewed

Growing up in the age of COVID-19 through the lens of psychodynamic theory - Grady, Melissa D.; O’Toole, Randall; Schneider, Dana A. (Psychoanalytic Social Work, 2021)
The long-term effects of the global COVID-19 pandemic on individuals, families, and society are not yet known. For social workers, it is critical to consider how the pandemic is impacting families, and in particular, children and their development. This manuscript applies psychodynamic theory and research on neurobiology to explore some of the potential effects of COVID-19 on children and their developmental trajectories. The discussion of these psychodynamic concepts is also placed within the context of the heightened tensions around equity and social justice issues within the U.S. society. In addition, this article provides guidelines, strategies, and resources for social workers that can be used when working with families and caregivers to mitigate any potential negative effects that the pandemic is having on children and their families. A case presentation is included to further illustrate these issues. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.swk; peer-reviewed

Group Well-Child Care and Health Services Utilization: A Bilingual Qualitative Analysis of Parents' Perspectives. - Oldfield, Benjamin J; Nogelo, Patricia F; Vazquez, Marietta; Ona Ayala, Kimberly; Fenick, Ada M; Rosenthal, Marjorie S (Maternal and child health journal, 2019)
Objective Alternative primary care structures such as group well-child care (GWCC) may enhance care for families, particularly those subject to structural vulnerabilities such as poverty or restrictive immigration policies. The purpose of this study was to characterize how group dynamics in GWCC impact the perceptions of low-income, immigrant, and/or Spanish-speaking parents of health services. Methods Using Spanish and English interview guides that were conceptually identical, we conducted semi-structured interviews with parents who elected to participate in GWCC at an urban academic center. We drew from directed content analysis, grounded theoretically in the Andersen model of health services utilization. Modeling a bilingual, multicultural analytic strategy, we preserved the narrative of participants in the source language through all stages of analysis. Results From March through August 2017, we interviewed 22 caregivers in their preferred language. Most (82%) were mothers and half spoke Spanish only. Three themes emerged: participants perceived that (1) GWCC facilitates their and their peers' discovery of inherent expertise, which moderates parents' use of health services, (2) GWCC encourages rearrangements of hierarchies of knowledge, professional roles and genders; and (3) in the context of structural vulnerabilities, relationships formed in GWCC facilitate collective efficacy. Conclusions for Practice By considering the self and peer as sources of health-related expertise, GWCC may extend current theoretical models of health services utilization. GWCC provides opportunities to impact health services utilization among families subject to structural vulnerabilities.
Keywords: *Child Health Services/sn [Statistics & Numerical Data]; *Child Welfare; *Parents/px [Psychology]; *Patient Acceptance of Health Care/sn [Statistics & Numerical Data]; Adolescent; Adult; Child Health Services; Child Welfare; Child, Preschool; Cultural diversity; Female; Humans; Interviews as Topic; Interviews as Topic/mt [Methods]; Male; Multilingualism; Parents; Patient Acceptance of Health Care; Patient Acceptance of Health Care/px [Psychology]; Primary health care; Qualitative Research; Qualitative research; Vulnerable populations; adolescent; adult; article; caregiver; case report; child; child care; child health care; child parent relation; child welfare; clinical article; content analysis; cultural diversity; dept.swk; drug efficacy; female; gender; group dynamics; health care utilization; human; human experiment; immigrant; interview; language; lowest income group; male; mother; multilingualism; narrative; patient attitude; peer-reviewed; perception; preschool child; primary health care; procedures; professional standard; psychology; qualitative analysis; qualitative research; semi structured interview; speech; vulnerable population

Replication data for Do Monetary Incentives Undermine Performance on Intrinsically Enjoyable Tasks? A Field Test - Esteves-Sorenson, Constanca; Broce, Robert (Harvard Dataverse, 2020)
Keywords: dept.swk

Development on purpose: Faith and human behavior in the social environment - Howe, Esther (Journal of Religion and Spirituality in Social Work, 2020)
Keywords: dept.swk; peer-reviewed

COVID-19 and Youth in Detention - Rowe, William (Child & Youth Services, 2020)
Keywords: dept.swk; peer-reviewed

Making Meetings Productive and Working with Groups for Social Workers - Rofuth, Todd W.; Piepenbring, Julie M. (Management and Leadership in Social Work: A Competency-Based Approach, 2020)
Keywords: dept.swk

Preface - Rofuth, Todd W.; Piepenbring, Julie M. (Management and Leadership in Social Work a Competency-Based Approach, 2020)
Keywords: dept.swk

Foreword - Rowe, William (Management and Leadership in Social Work: A Competency-Based Approach, 2020)
Keywords: dept.swk; ⛔ No DOI found

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

The past and future of social group work in Germany: contributions of Louis Lowy - Gardella, Lorrie Greenhouse (Social Work with Groups, 2021)
Louis Lowy (1920 to 1991), the international social work educator, remembered surviving the Holocaust as a formative professional experience. After joining the faculty of Boston University School of Social Work, Lowy returned to Germany every summer for 20 years to help restore social work education. This SPARC project, “The Past and Future of Social Group Work in Germany: Contributions of Louis Lowy,” was proposed in collaboration with Klaus-Martin Ellerbrock and the German Chapter of IASWG at the height of the 2015 global refugee crisis, when Germany admitted more than one million refugees. The purposes of the project were to encourage ongoing international scholarship on the implications of Lowy’s teachings for social work with groups; to facilitate research and writing from an international perspective on group work with migrants and other disenfranchised populations; and to foster international collaborations among group workers in the spirit of Louis Lowy. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.swk; peer-reviewed

Masculine embodiment among sexual minorities in a women’s prison - Smoyer, Amy B.; Divita, David; Perrault, Allison (Australian Social Work, 2021)
Sexual minority women are disproportionately incarcerated and more likely to experience structural and interpersonal violence while incarcerated than heterosexual cisgender women. To build knowledge about this population and inform social work practice, theories of embodiment were used to conduct thematic analysis of five interviews with lesbian, gay, bisexual, transgender, and queer masculine-identified people who had been incarcerated in a women’s prison. This analysis explicates how participants used bodily practices to construct gender and communicate identity to themselves and others. Uniforms, prison regulations, and physical manifestations of female embodiment complicated these efforts. Participants described the ways in which they monitored and evaluated their own bodies while also managing the constant surveillance of their bodies by others. Taken together, these findings explicate the ways in which participants’ bodies were produced both through their actions and the external gaze of others. Implications for social work include exploration of language and masculinity in practice settings and suggestions for correctional policies. Findings encourage inclusion of non-binary frameworks and increased attention to the embodied self in order to expand understandings of human behaviour in the social environment. IMPLICATIONS Interpret with caution any information about gender identity surmised from intake forms and observation of clients’ bodily practices. Ask clients to describe their gender identity. Prioritise correctional policies that promote the health and safety of incarcerated people and staff over policies that enforce social norms related to gender and have no implications on security. Encourage re-entry service providers to collaborate with LGBTIQA+ organisations that provide social support to clients who identify as sexual minorities. © 2021 Australian Association of Social Workers.
Keywords: LGBTQIA+ people; adult; article; attention; correctional facility; dept.swk; female; gaze; gender identity; human; interview; language; male; masculinity; organization; peer-reviewed; security; social environment; social norm; social support; social work practice; thematic analysis

‘Suppression on top of oppression’: A symbolic interactionist perspective on the affective experience of incarceration - Umamaheswar, Janani (The British Journal of Criminology, 2021)
Penological research has extensively documented how incarcerated men's identities are shaped by the prison setting, highlighting how these men cope with and adapt to the 'pains of imprisonment' through careful emotion management. Significantly less research has focused explicitly on the role of emotion in incarcerated men's constructions of their selves. In this article, I draw on 24 in-depth interviews with incarcerated men to reveal how the prison setting generates negative emotions (such as sadness, shame, humiliation, and anger) that in turn perpetuate the isolation that these men face. Emotions thus constitute an overlooked source of these men's social marginalization. Additionally, I draw on theoretical literature derived from symbolic interactionism (and identity theory in particular) to explore how participants cope with, and make efforts to overcome, their negative emotions by engaging in active emotion and identity work centred on constructing morality narratives of pride, self-worth, and superiority. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of the Centre for Crime and Justice Studies (ISTD). All rights reserved.
Keywords: dept.swk; peer-reviewed

Helps my family survive hard times: An innovative summertime food relief program in new haven, connecticut - Zigmont, V.A.; Tomczak, S.M.; Bromage, B.; Vignola, A.; Gallup, P (Journal of Poverty, 2021)
To achieve healthy communities, addressing food insecurity (FI) is critical. This study describes a unique food distribution program combining a mobile Summer Food Service Program (SFSP) for children with a mobile pantry for adults. A survey (n = 153) of participants at six locations in New Haven Connecticut revealed that 36% reported FI and 76% were first-time pantry users. Three- quarters participated in SNAP, WIC, or both, and two-thirds had children who were fed by SFSP. Major federal programs do not eliminate FI, therefore local voluntary organizations are essential partners to address the food crisis caused by the COVID-19 pandemic.
Keywords: dept.pch; dept.swk; peer-reviewed

Teaching individualized sexuality education to a young boy with autism spectrum disorder in the least restrictive environment: A case study - Albee, Laura J. (Advances in Early Childhood and K-12 Education, 2020)
Keywords: dept.swk

Do monetary incentives undermine performance on intrinsically enjoyable tasks? A field test - Esteves-Sorenson, Constança; Broce, Robert (The Review of Economics and Statistics, 2022)
Economists have long been intrigued by an influential literature in psychology positing that monetary pay lowers performance on enjoyable tasks by crowding out agents’ intrinsic interest in them. But typical experiments in this literature do not report a full set of performance metrics, which might reveal conflicting evidence on crowding out. Further, they may suffer from confounds. To evaluate these issues, we review over 100 prior tests and run a field experiment building on the canonical two-session test for crowding out wherein agents receive pay for an interesting activity in session 1 that is withdrawn unexpectedly in session 2. We test whether pay harms performance using a comprehensive set of performance measures, and if so, whether unmet pay expectations might also contribute to this decline. Our results on output, productivity and quits are most consistent with a standard economics model than with a crowding-out one. Additional, though more speculative, evidence suggests that unmet pay expectations may harm output quality. © 2020 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.
Keywords: dept.swk; peer-reviewed

Re/Un/Discover: An embodied heuristic for uncertainties in social work practice - Keenan, Elizabeth King (Australian Social Work, 2021)
Social workers have always worked with and within uncertainties in practice, but the COVID-19 pandemic is amplifying the frequency and degree of uncertainty across ecological levels. Social workers need enhanced capacity to work with these uncertainties and the impact on individual and collective wellbeing. The RE/UN/DIScover heuristic guides social workers’ responses to the wide range of practice uncertainties experienced in the moment and over time. Drawing on understandings of embodied wellbeing from interpersonal neurobiology and the power relations manifest in intersectional positionality, RE/UN/DIScover offers embodied, iterative practices to access the wealth of capabilities within self and others. IMPLICATIONS Disruptions and uncertainties connected with pandemics, economic recessions, continued systemic injustices and other human-made problems can challenge social workers and impact the wellbeing of individuals and communities. Heuristics are guides that sort, order, and inform decisions and actions. The RE/UN/DIScover heuristic uses knowledge about embodied wellbeing and various forms of power to guide social workers. RE/UN/DIScover offers social workers practices to use with uncertainties both in the moment and over time. © 2020 Australian Association of Social Workers.
Keywords: dept.swk; peer-reviewed

An ecological framework for understanding HIV- and AIDS-related stigma among Asian American and Pacific Islander men who have sex with men living in the USA - Sen, Soma; Aguilar, Jemel P.; Petty, Mac (Culture, Health and Sexuality, 2021)
Despite the fact that HIV- and AIDS-related stigma is consistently identified as an impediment to HIV prevention, a multilevel conceptualisation of HIV- and AIDS-related stigma continues to be poorly understood. The role of multilevel HIV- and AIDS-related stigma in the HIV prevention and intervention behaviours of Asian American and Pacific Islander who have sex with men in the USA is particularly overlooked. Psychology has contributed significantly to the identification of individual or interpersonal level factors influencing HIV- and AIDS-related stigma, while sociology has contributed to a more societal perspective. This dichotomy has led to the absence of a multilevel conceptual framework for analysing the HIV- or AIDS-related stigma experienced by Asian American and Pacific Islander who have sex with men in the USA. In this paper, we argue for need to develop such a model which is culturally grounded and bridges the individual, interpersonal and societal conceptualisations of stigma prominent in the social science literature. To that end, we use Bronfenbrenner’s ecological systems theory to explore the manifestation of HIV stigma at the micro, meso and macro levels and how these might impact on HIV testing and HIV service utilisation among Asian American and Pacific Islander men who have sex with men. We conclude by identifying some practice and research implications.
Keywords: Acquired Immunodeficiency Syndrome; Asian American; Asian Americans; HIV Infections; Homosexuality; Human immunodeficiency virus infection; Humans; Male; Sexual and Gender Minorities; United States; acquired immune deficiency syndrome; dept.swk; human; male; male homosexuality; peer-reviewed; sexual and gender minority

Tensions and connections between social work and anti-capitalist disability activism: disability rights, disability justice, and implications for practice - Eiler, Elijah C.; D'Angelo, Karen (Journal of Community Practice, 2020)
Social work’s relationship to disability activism under capitalism is an underexplored area of the profession’s literature. This paper aims to help address this gap by providing a conceptual discussion of the tensions within disability activism, within social work, and between the two. Lenin’s analysis of the state is used to integrate opposing ideologies. We begin by providing a historical overview of the disability rights and disability justice movements along with recommendations for an integrated approach. We then connect ideological trends within social work to these models. We end with implications for social work practice with disabled people and suggested research. © 2020 Taylor & Francis Group, LLC.
Keywords: Lenin; Radical social work; anarchism; dept.swk; disability justice; disability rights; mutual aid; peer-reviewed

A case for developing the emotional capacities of social workers: A commentary on “Promoting self-awareness: Infant observation training as a model” - Bliss, S (Smith College Studies in Social Work, 2005)
Keywords: dept.swk; ⚠️ Invalid DOI

Mass trauma and violence: Helping families and children cope. - Dripchak, VL (Clinical Social Work Journal, 2005)
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2005)
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2005)
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 3 - Keenan, EK (Clinical Social Work Journal, 2005)
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 4 - Keenan, EK (Clinical Social Work Journal, 2005)
Keywords: dept.swk

Parallel processes in community- based research - Keenan, Elizabeth King (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2005)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Micro ruptures and repairs in the beginning phase of cross-cultural psychotherapy - Keenan, Elizabeth; Tsang, A.; Bogo, Marion; George, Usha (Clinical Social Work Journal, 2005)
The article discusses misunderstandings and misattunements that occur in the beginning phase of cross-cultural psychotherapy. Sources of micro ruptures are outlined, including client maladaptive patterns, therapist misunderstandings, cross-cultural misunderstandings due to cultural variations, and asymmetrical power relations involving the impact of prior experiences or current therapy practices. Multiple clinical vignettes illustrate the rupture/repair process, drawing on Safran and Muran's (2000) list of direct and indirect techniques., (C)2005 Kluwer Academic Publishers
Keywords: Beginning phase of psychotherapy; Cross-cultural psychotherapy; Rupture and repair; Therapeutic relationship; beginning phase of psychotherapy; cross-cultural psychotherapy; dept.swk; rupture and repair; therapeutic relationship

Do social workers integrate sociocultural issues in mental health session dialogue?: an exploratory study of cross-cultural practice - Keenan, Elizabeth King; Tsang, A. Ka Tat; Bogo, Marion; George, Usha (Social Work in Mental Health, 2004)
Keywords: dept.swk

From sociocultural categories to socially located relations: Using critical theory in social work practice - Keenan, EK (Families in Society-the Journal of Contemporary Human Services, 2004)
This article applies concepts from critical social theories to shift the profession's discourse from the center-margin relations of generalist-multicultural practice to a model of socially located cross-cultural client-worker relationships. Critical theories examine patterns and meanings enacted within and between people in specific social locations at specific points in history that express particular relations of culture, power, and identity. This framework can help social workers listen, explore, conceptualize, and intervene in a more complex and effective manner. The article summarizes key themes in critical theories, redefines how social workers can use knowledge for practice, and concludes with discussion of a case illustration.
Keywords: dept.swk

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
Keywords: dept.swk

Culture and psychoanalytic theory - Introduction to the book reviews - Keenan, EK (Clinical Social Work Journal, 2004)
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2004)
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2004)
Keywords: dept.swk

Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
Keywords: dept.swk

Whole-school violence prevention program: A university-public school collaboration - Haymes, Elayne; Howe, Esther; Peck, Lynne (Children & Schools, 2003)
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2003)
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 3 - Keenan, EK (Clinical Social Work Journal, 2003)
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 4 - Keenan, EK (Clinical Social Work Journal, 2003)
Keywords: dept.swk

Book Review: object relations theory and self psychology in social work practice. eda g. goldstein. new york: the free press, 2001, 303 pp., 35.00 - Keenan, Elizabeth King (Clinical Social Work Journal, 2002)
Keywords: book.review; dept.swk

Ethnographic study of gay and bisexual working-class men in the united states - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
Keywords: dept.swk

An ethnographic study of six latino gay and bisexual men - Colon, Edgar (Journal of Gay and Lesbian Social Services, 2001)
Keywords: dept.swk

Distance learning in gerontological education: results and implications of a national survey - Tompkins, Catherine J.; Siegel, Elbert (Gerontology & Geriatrics Education, 2001)
This article reports data collected from a national survey of the Association for Gerontology in Higher Education’s (AGHE) member institutions conducted in 1998. The purpose was to explore current usage of distance learning in gerontological education. The findings suggest that distance learning is being implemented within various programs throughout the country with many others showing an interest. The strengths and limitations of using distance learning in gerontological education are discussed. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-342-9678. E-mail address: <getinfo@haworthpressinc.com> Website: <http://www.HaworthPress.com>]. © 2001 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.swk

Ethnographic study of twenty-six gay and bisexual working-class men in australia and new zealand - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
Keywords: dept.swk

Implications for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
Keywords: dept.swk

Interviewing working-class gay men over the internet - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
Keywords: dept.swk

Practice and theoretical knowledge-based theory for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
SUMMARY: Practice with working-class gay and bisexual men draws upon an ecological framework with a strengths perspective, which emphasizes the roles of culture, values, social class, social identity development, social categorization, social comparison, oppression and power, diversity, and stigma. This practice is based upon a process of developing an assessment and selecting a range of human service interventions. Ethnographic studies were conducted throughout the United States and Canada using a broad-based sample of working-class men to enhance our understanding of their needs and effective ways of helping. © 2001, Taylor & Francis Group, LLC.
Keywords: And intervention; Assessment; Culture; Diversity; Ecology; Individual and group identity; Oppression and power; Social class; Stigma; Strengths; Values; dept.swk

"It was just realizing... that life isn't one big horror": A qualitative study of supported socialization - Davidson, L.; Haglund, K.E.; Stayner, D.A.; Rakfeldt, J.; Chinman, M.J.; Tebes, J.K. (Psychiatric Rehabilitation Journal, 2001)
This report describes the qualitative component of a large-scale study of supported socialization. Paralleling the recent advances made through supported housing, supported employment, and supported education, this approach seeks to increase the involvement of individuals with psychiatric disabilities in naturally occurring social and recreational activities in community settings of their choice. After a review of social relationships and psychiatric disability, we describe the Partnership Project and present findings from a series of qualitative interviews conducted with a subsample of participants. We then discuss the implications of these findings for the community integration of individuals with psychiatric disabilities.
Keywords: adult; article; clinical article; dept.swk; education; employment; female; health program; housing; human; human relation; integration; life; male; mental disease; questionnaire; recreation; socialization; support group; therapeutic community

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Teaching organization theory and practice: an experiential and reflective approach - Cameron, Mark; Turkiewicz, Rita M; Holdaway, Britt A; Bill, Jacqueline S; Goodman, Jessica; Bonner, Aisha; Daly, Stacey; Cohen, Michael D; Lorenz, Cassandra; Wilson, Paul R; Rusk, James (Journal of Teaching in Social Work, 2009)
The organization is often the overlooked level in social work's ecological perspective. However, organizational realities exert a profound influence on human development and well-being as well as the nature and quality of social work practice. This article describes a model of teaching organization theory and practice which requires master's social work students to assess their school of social work as well as their field placement agencies. Teaching organization theory and practice experientially may help students understand how organizations influence practice and empower them to see organization practice as a legitimate and important aspect of their work.
Keywords: Field education; Macro; Organization; Practice; Teaching; dept.swk; peer-reviewed

Book Review: Run: A novel - Rakfeldt, Jaak (Psychiatric Services, 2008)
Keywords: book.review; dept.swk

Refusing the right to refuse: Coerced treatment of mentally disordered persons - Rakfeldt, Jaak (Psychiatric Services, 2008)
Keywords: dept.swk

Crisis intervention handbook: Assessment, treatment, and research - Bliss, Susan (Smith College Studies in Social Work, 2008)
Keywords: dept.swk

Third Space Activities and Change Processes: An Exploration of Ideas from Social and Psychodynamic Theories. - Keenan, Elizabeth; Miehls, Dennis (Clinical Social Work Journal, 2008)
Discussions pertaining to culture, power and/or identity frequently create tensions that are enacted by dyads and groups within schools, workplaces and communities. Although tensions can easily escalate into conflict or violence, we have observed that these tensions can serve as prompts that promote a change process. When individual perspectives are challenged, some participants are able to dissemble their views and consider other perspectives from which new understandings and views emerge. At times, when groups seem to be on the threshold of overt conflict, some participants engage in processes that examine the tension, explore new possibilities, and alter the view of one's subjectivity. We suggest that these activities occur as momentary states in psychological spaces conceptualized as third spaces (Bhabha, The location of culture. London: Routledge, 1994). In this paper, we use concepts from psychodynamic and social theories to describe the conditions that coalesce to form states of mind (nepantla) (Anzaldua, Borderlands/La Frontera: The new mestiza. San Francisco: Aunt Lute Books, 1999; Interviews Entrevistas. New York: Routledge, 2000) and the ability to engage in new relational possibilities (third space activities) with dyads and groups, outside of psychotherapy. The conditions include: critical consciousness, regulation, recognition, and responsibility. We then describe how such momentary experiences can subsequently result in an examination of one's subjectivity, particularly as it pertains to issues regarding culture, power, and identity. Throughout the paper we provide four examples from various settings to illustrate these concepts and processes. Given the increasing racial/ethnic diversity of clients and clinical social workers in North America, this concept of third spaces holds particular relevance for contemporary clinical social work practice., (C)2008 Kluwer Academic Publishers
Keywords: Change processes; Psychodynamic theory; Social theory; Third space activities; dept.swk

Reflections from a student of mothering - Schneider, Dana (Smith College Studies in Social Work, 2008)
This reflective article provides a window into one clinical social worker's experience of returning to school after becoming a mother. The convergence of two separate lives, those of mother and student, is explored through a psychodynamically-informed perspective. Challenges of integrating theories on mothering from an experience-near position are discussed.
Keywords: dept.swk

Posttraumatic play: Towards acceptance and resolution - Dripchak, Valerie L. (Clinical Social Work Journal, 2007)
Many children who experience trauma demonstrate it through posttraumatic play (PTP). This type of play is seen by professionals as a repetitive reenactment of the traumatic event within the child's play. Reliving the event in this way may serve to retraumatize the child and lead to other psychiatric or behavioral problems. This article examines the issues surrounding childhood trauma and PTP. It uses a case study to illustrate the phases of a play therapy approach that incorporates Ericksonian principles, in order for the child to achieve resolution and acceptance. The countertransference issues that a clinician may encounter also are discussed.
Keywords: Play therapy; Posttraumatic play; Retraumatize; Trauma in children; dept.swk

Lesbian mothers with planned families: A comparative study of internalized homophobia and social support - DeMino, Kathleen A.; Appleby, George; Fisk, Deborah (American Journal of Orthopsychiatry, 2007)
This study compared the perception of social support and the degree of internalized homophobia for two demographically similar groups: lesbians with planned families and lesbians who did not have children. Results found that lesbians with planned families perceived significantly less social support from friends overall, from gay men and lesbian friends specifically, and more support from their families-of-origin than lesbians who did not have children. Lesbians with planned families also reported significantly higher internalized homophobia specific to disclosure of sexual identification. The authors suggest that selective disclosure may be an adaptive response rather than a true measure of internalized homophobia.
Keywords: Adult; Attitude; Child; Family Planning Services; Female; Homosexuality, Female; Humans; Internalized homophobia; Lesbian mothers; Maternal Behavior; Mothers; Percerption of social support; Planned families; Questionnaires; Self Concept; Social Support; adult; article; controlled study; demography; dept.swk; family; female; gender identity; homophobia; human; lesbian; male homosexual; social support

Diagnosing conduct problems of children and adolescents in residential treatment - Cameron, Mark; Guterman, Neil B (Child Care Quarterly, 2007)
This naturalistic study of diagnostic practice in residential treatment agencies for children investigated the use of the DSM-IVconduct disorder diagnosis and its association with residents' externalizing behaviors. The conduct disorder (CD) diagnosis was a poor predictor of participants' externalizing behaviors during their first few months in residence. Additionally, the assignment of the diagnosis was associated with the gender and race of study participants. Decisions of admissions personnel and practitioners in residential treatment facilities regarding their externalizing clients may not be well-served by use of DSM diagnoses. Assessments of caregivers may prove a useful adjunct to DSM diagnoses. © 2007 Springer Science+Business Media, LLC.
Keywords: Adolescents; Children; Conduct disorder; DSM-IV validity; Diagnosis; Residential treatment; dept.swk

Patterns of interaction: Conceptualizing the crossroads between social structures, interpersonal actions, and psychological well-being - Keenan, Elizabeth King (Smith College Studies in Social Work, 2007)
Patterns of interaction theory directs social workers' attention to the relations between structures (psychological and social), and actions: the crossroads of continuity and change. Because it describes sequences of action by key participants that generate specific options at various points in a sequence, it serves as both theory and method for understanding and intervening with human beings and social structures. The use of patterns of interaction as an overarching construct illuminates the reciprocal relationships between social structures, interpersonal actions, and psychological well-being. This paper outlines a preliminary conceptualization of patterns of interaction theory and the methodology that grows out of it. The social service programs of Temporary Assistance to Needy Families (TANF) and a community-based case management welfare-to-work program illustrate how an ethical lens applied to patterns of interaction can help social workers intervene within complex relations to facilitate client growth. Patterns of interaction theory is a potentially effective way of describing and analyzing the therapeutic effects of a range of different social service programs.
Keywords: dept.swk; ⚠️ Invalid DOI

The good life - Rakfeldt, Jaak (Psychiatric Services, 2006)
Keywords: dept.swk

Assertive outreach: An effective strategy for engaging homeless persons with substance use disorders into treatment - Fisk, Deborah; Rakfeldt, Jaak; McCormack, Erin (American Journal of Drug and Alcohol Abuse, 2006)
The purpose of this study was to examine substance abuse treatment referrals that were made by outreach workers in a homeless outreach project. Ten outreach workers completed questionnaires on each of their clients who they had referred to a substance abuse treatment program over the previous year. Additional data was collected on the client's motivation level at the point the referral was made, which agencies the client was referred to, and if the client was rejected from any of the treatment programs. Bivariate correlation analyses were used to examine relationships between the variables. Of 73 project clients who were referred to substance abuse treatment in a one-year period of time, 41% successfully entered treatment. As might be expected, there was a statistically significant relationship between clients' motivation level and completed referral, and between referrals made and program acceptance. This study provides evidence that assertive outreach is effective in engaging and linking homeless persons with substance use disorders to substance abuse treatment services.
Keywords: Adolescent; Adult; Assertive outreach; Community-Institutional Relations; Female; Homeless Persons; Homeless populations; Humans; Male; Middle Aged; Substance abuse; Substance-Related Disorders; Treatment Outcome; adult; article; assertiveness; correlation analysis; dept.swk; drug dependence treatment; female; homelessness; human; major clinical study; male; mental health service; motivation; patient referral; social work; social worker; statistical significance; substance abuse

My father the spy: An investigative memoir - Rakfeldt, J (Psychiatric Services, 2006)
Keywords: dept.swk

Weight bias: Nature, consequences, and remedies. - Howe, Esther (Clinical Social Work Journal, 2006)
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2006)
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 2 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 3 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 4 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
Keywords: dept.swk

Feeding relationships: foodways and social networks in a women’s prison - Smoyer, Amy B. (Affilia, 2014)
Research has demonstrated the importance of supportive relationships and social networks to prisoners’ psychosocial outcomes, especially for women. Understandin...
Keywords: dept.swk; peer-reviewed

Dealing food: Female drug users’ narratives about food in a prison place and implications for their health - Smoyer, Amy B.; Blankenship, Kim M. (International Journal of Drug Policy, 2014)
Keywords: dept.swk

Setting the stage: creating study sites that promote the safety and dignity of research participants - Smoyer, Amy B.; Rosenberg, Alana; Blankenship, Kim M. (Social Work Research, 2014)
The U.S. Department of Health and Human Services' (HHS) Code of Federal Regulations regarding Protection of Human Subjects (45 C.F.R. part 46) provides guidance
Keywords: dept.swk

Being on the mat: a process evaluation of trauma-informed yoga for women with substance use disorders - Smoyer, Amy (The Journal of Sociology & Social Welfare, 2016)
Yoga practice is associated with positive health outcomes, including benefits related to managing substance use disorders and trauma symptomology. However, low-income vulnerable communities have limited access to yoga. This process evaluation of a trauma-informed yoga program for women with substance use disorders demonstrates the feasibility and utility of using noncertified yoga instructors to offer a basic yoga in community-based agencies. Participants describe outcomes related to relaxation, mindfulness, and movement that are well-aligned with their recovery needs. Study findings suggest the utilization of instructors with minimal training has the potential to expand research about and access to yoga among marginalized communities. © 2016, Western Michigan University. All rights reserved.
Keywords: Evaluation; Qualitative; Substance use; Women; Yoga; dept.swk; ⛔ No DOI found

Mapping prison foodways - Smoyer, A.B. (Experiencing imprisonment: research on the experience of living and working in carceral institutions, 2016)
Keywords: dept.swk

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed

Constructing the Reproductive Behavior of Poor People: Regulating Procreation by Public Aid Recipients from Malthus to Murray - Tomczak, Stephen Monroe (Social Service Review, 2020)
Keywords: dept.swk; peer-reviewed

The everything else - Smoyer, Amy B. (Sensory Penalities, 2021)
Sensory Penalties aims to reinvigorate a conversation about the role of sensory experience in empirical investigation. It explores the visceral, personal reflections buried within forgotten criminological field notes, to ask what privileging these sensorial experiences does for how we understand and research spaces of punishment and social control.
Keywords: dept.swk

Ping-pong housing: Women’s post-incarceration trajectories - Smoyer, Amy B; Keene, Danya E; Oyola, M.; Hampton, A (Affilia, 2020)
This study examines the post-incarceration housing experiences of 33 women. Using Residential Timeline Followback methodology, participants were asked to report where they lived at arrest and every location since their release. Follow-up questions asked women to describe these locations, who they lived with, how much they paid, and whether or not they felt safe. Demographic information and criminal justice history were recorded. The data paint a complicated picture of social and community resources, persistence, and struggle. Housing assets lost at incarceration were difficult to recover. Most women bounced between various locations, relying heavily on short-term subsidized congregate housing programs and rarely securing independent housing. Participants described the family, friends, and acquaintances who housed them during reentry as overextended and vulnerable. Implications for policy and practice are explored. © The Author(s) 2020.
Keywords: dept.swk; peer-reviewed

“When my mother died, I think a part of me died:” maternal fusion and the relationship between incarcerated men and their mothers - Umamaheswar, J. (Journal of Family Issues, 2021)
Drawing on theoretical literature on the mothering discourse, I explore how incarcerated men give meaning to their relationships with their mothers. Using 24 in-depth interviews with incarcerated adult men, I argue that adherence to the mothering discourse results in sons holding their mothers’ maternal practices to impossibly high standards while simultaneously feeling obligated to reconcile with their mothers even when doing so is tremendously difficult. I also advance the concept of “maternal fusion”—the process through which the identities of mothers and their children are intertwined—to examine how incarcerated adult sons reproduce gendered mothering ideologies in their narratives of (a) negative early childhood and adolescent relationships with their mothers and (b) reconciliation as they reflect on their relationships with their mothers as adult sons.
Keywords: adolescent; adult; article; child; childhood; dept.soc; dept.swk; drawing; female; human; human experiment; ideology; incarceration; infant; interview; male; maternal fusion; mother; mothering; mothering discourse; narrative; peer-reviewed; theoretical study

Fragmented images: how can the eye see itself? A relational and intersubjective reformulation of cross-cultural therapy with cecilia - Pizzanello, Heather (Psychoanalytic Social Work, 2015)
This article discusses why it is crucial in the cross-cultural clinical encounter to practice from both Jessica Benjamin's intersubjective frame as well as relational theory when the therapist is from the dominant White culture and the client is African American. Intersubjective and relational theories are utilized to illustrate how it is in this clinical situation, however, that some therapists may find themselves avoiding the use of a more relational practice. A case illustration is presented from the lens of Winnicott's theory of object relations to convey the dynamic complexities that may impede a therapist from practicing out of these (more relational) frames and then the case is reconceptualized from both a relational and intersubjective perspective. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: Winnicott; cross-cultural therapy; dept.swk; intersubjectivity; peer-reviewed; relational practice

Reflections on the process of evolving from a student of literature to a social work instructor of humanism - Pizzanello, Heather (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2015)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Making fatty girl cakes: food and resistance in a women's prison - Smoyer, Amy B. (The Prison Journal, 2016)
This article builds on existing knowledge of inmate resistance by analyzing formerly incarcerated women's narratives about prison food. Participants described trying to secure extra cafeteria portions, hoarding food, smuggling and stealing food, and cooking and eating in the cellsall to resist prison power and gain some control over their lives by managing what, how, when, and with whom they ate. These data shed light on prison life and suggest changes to food policy to curb inmate resistance and bolster the rehabilitative potential of correctional facilities.
Keywords: dept.swk; food; prisoners; resistance; women

Applying research to enhance capacity: A unifying purpose for an integrated profession - Keenan, Elizabeth King (Journal of Social Work Education, 2016)
For more than a century the social work profession has had a dual purpose: to promote individual well-being and social justice, but the micro-macro divide is fragmenting the profession. This article suggests that the profession's aim might best be realized by adopting a unifying purpose, a just sense of well-being. Research on complex adaptive systems conceptualizes a unifying purpose as vertical integration carried out in differentiated ways in discrete moments of practice in various settings. Interpersonal neurobiology and Aristotle's interdependence of character virtues and practical judgment inform a corresponding shift from the dualities of personal and professional to the social worker as a person with differentiated professional capacities and activities. Integration with differentiation enhances capacity to promote the profession's purpose.
Keywords: dept.swk; differentiation; human; human experiment; morality; neurobiology; occupation; peer-reviewed; social justice; social work; wellbeing

Meeting at the thin places: synchronicities in clinical practice - Schneider, Dana A. (Smith College Studies in Social Work, 2016)
Unusual events, beyond mere coincidences, may occur during the course of psychotherapy. Yet, clinical training often does not prepare therapists how to understand and potentially engage with these encounters. The aim of this report is to explore the emergence of synchronistic events in therapy, while providing two clinical case composites to illustrate the author's central points. Drawing on the Celtic concept of thin places, a new understanding of synchronicities and the therapeutic relationship is offered.
Keywords: Internal structure; dept.swk; synchronicity; therapeutic relationship; thin places; unconscious communication; unknown

Home environments, memories, and life stories: preservation of estonian national identity - Rakfeldt, Jaak (Journal of Baltic Studies, 2015)
This paper examines the means by which Estonian national identity was preserved during 50years of Soviet occupation. The study upon which it is based explored such factors as family environments; memories, in the form of oral narratives; and life experiences. This research was informed by the sociocultural approach to mediated action, and it employed both quantitative and qualitative research methods. In 1993, a quota-sampling technique was used to interview a cross section of Estonian society (N=930). Descriptive statistics, and factor and multiple regression analyses were performed. Fifteen qualitative interviews were also conducted. When woven together, these personal histories create a fabric that is representative of the greater Estonian history during the occupation. The implications of these findings may reach beyond the Estonian context to further inform our understanding of the complexities and the vicissitudes of human action.
Keywords: Estonian national identity; dept.swk; life stories; social memory; song festivals; “The Singing Revolution”

Full employment as a permanent policy response to poverty - Tomczak, Stephen Monroe; Rofuth, Todd W. (Journal of Community Practice, 2015)
Rising inequality and concomitant economic insecurity and poverty is a continuing problem in the United States today. Enacting full employment policies would resolve this problem and would serve as a viable poverty reduction strategy. Using a more accurate measure of unemployment such as the Bureau of Labor Statistics U-6 measure would reveal the true unemployment rate. This article provides different strategies, historical and more recent, for enacting full employment with a living wage, particularly the enactment of a permanent national public service employment program administered by the states through the TANF Emergency Fund. Public sector employment expansion in the green or clean economy would benefit the urban unemployed the most. To achieve these ends, social workers, unions and community activists will need to collaborate. Finally, the Federal Reserve should review the history of the relationship between unemployment and inflation rates and develop a more accurate formula for attaining full employment while keeping inflation low. Copyright © Taylor & Francis Group, LLC.
Keywords: United States; dept.swk; economic inequality; emergency; employment; full employment; human; human experiment; peer-reviewed; policy; poverty; social worker; statistics; unemployment

The moderating effect of positive father engagement and accessibility on a school-based system of care intervention for mental health outcomes of children - Bernard, Stanley N; Whitson, Melissa L; Kaufman, Joy S (Journal of Child and Family Studies, 2015)
We conducted an exploratory research study looking at fathering interactions as they relate to the wraparound care given by the Partnership for Kids or PARK Project, a school-based system of care in Bridgeport, Connecticut. The questions posed by our research focused on how fathers' positive interaction measured by their levels of engagement and accessibility can moderate the effect of the school-based system of care intervention on the mental health outcomes of children with serious emotional disturbances. We found that, although not statistically significant, children's access to their father did have a moderating effect on CBCL scores for internalizing behaviors and total problems. There was very small change in CBCL scores for externalizing behaviors. Further, the moderating effect of father accessibility and father engagement had a lasting effect as a moderator through 12 months into the intervention, especially with regard to internalizing behavior scores.
Keywords: Children’s mental health; Fatherhood; Systems of care; dept.swk

Conscious and unconscious use of self: the evolution of a process - Schneider, Dana A; Grady, Melissa D (Psychoanalytic Social Work, 2015)
Recent emphasis has been placed on the central role of the therapeutic relationship in successful treatment. One aspect of the development of an effective relationship is the clinical social worker's use of self. We argue that the use of self happens both consciously and unconsciously and is a dynamic and evolving process in psychotherapy. This evolution can result in the clinical social worker shifting from a stance of doing to being. Drawing from a Japanese tradition of learning, three stages of learning provide a framework for understanding how therapists may transition from a state of doing to being in the therapy. Through this process, the conscious use of self may develop into unconscious use of self. Two case examples demonstrate how expanding and using one's self-awareness and the new knowledge through meaningful learning experiences can shift a clinical social worker's ability to develop and enhance his or her use of self, inviting therapeutic presence and depth. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: conscious; dept.swk; peer-reviewed; therapeutic presence; therapeutic relationship; unconscious; use of self; way of being

From being known in the classroom to “Moments of meeting”: what intersubjectivity offers contemplative pedagogy - Schneider, Dana A; Keenan, Elizabeth King (The Journal of Contemplative Inquiry, 2015)
Keywords: dept.swk; ⛔ No DOI found

“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
Keywords: dept.swk

Confining legitimacy: the impact of prison experiences on perceptions of criminal justice legitimacy - Smoyer, Amy B; Kershaw, Trace; Blankenship, Kim M (Journal of forensic social work, 2015)
Keywords: dept.swk

Reflections on an experiential poverty simulation filtered through the mind’s eye of three faculty members - Tomczak, Stephen Monroe; Pizzanello, Heather; Schneider, Dana A (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2015)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Hunger in a “Land of plenty”: A renewed call for social work action - Libal, Kathryn; Tomczak, Stephen Monroe; Spath, Robin; Harding, Scott (Social Work, 2014)
Keywords: Child; Cooperative Behavior; Cross-Sectional Studies; Financing, Government; Food Assistance; Food Supply; Forecasting; Humans; Hunger; Interdisciplinary Communication; Politics; Poverty; Social Welfare; Social Work; Socioeconomic Factors; United States; catering service; child; cooperation; cross-sectional study; dept.swk; economics; financial management; food assistance; forecasting; human; hunger; interdisciplinary communication; organization and management; politics; poverty; social welfare; social work; socioeconomics; statistics and numerical data; trends

This is common factors - Cameron, Mark (Clinical Social Work Journal, 2014)
Common factors are conditions and processes present in, among, and surrounding participants in clinical work. In the past 20 years, increasing attention and research on common factors has generated a great deal of discussion in clinical psychology, psychiatry, marriage and family therapy, and to a lesser extent, social work. While there is no single definition of common factors, they are generally discussed as the non-technical aspects of therapeutic work-such as the relationship between the practitioner and client and the expectancy of the client-that have been shown to be associated with successful outcomes. Common factors also include attributes of the practitioner and client, the support system of the client, the institutional and organizational conditions in which the practitioner practices, and also the strategic actions employed by the practitioner, client, and all those involved in the work that promote change. This paper will discuss key concepts in a common factors practice perspective and how evidence is used by common factors practitioners, highlight features of common factors practice, and suggest implications for developing a common factors practice approach.
Keywords: Common factors; Evidence; Practice research; Technique; Therapeutic relationship; dept.swk

Beyond the manual: using research and evidence in social work practice - Grady, Melissa D.; Keenan, Elizabeth King (Clinical Social Work Journal, 2014)
There is a growing divide in social work between those that believe social work interventions should be based on either art or science. We argue that these positions create a false dichotomy within the profession, possibly due to the language associated with clinical work and research. In this introduction article of the Special Issue: Beyond the Manual, we outline the debate within social work around the art and science split and then offer a new approach to framing the issue. We argue that social workers are regularly approaching their work with clients using art and science simultaneously and describe a new frame for the profession. In an effort to articulate and promote this new frame, this special issue was born. This introductory article concludes with a brief description of the topics and articles included in the issue to orient the reader to the content included within it.
Keywords: Clinical judgment; Common elements; Common factors; Evidence-based practice, empirically-supported interventions; Research; dept.swk

From silos to scaffolding: engaging and effective social work practice - Keenan, Elizabeth King; Grady, Melissa D. (Clinical Social Work Journal, 2014)
In this final article of the special issue Beyond the Manual: Using Data and Judgment in Clinical Social Work Practice, we extend the discussion regarding the use of data and judgment. We discuss the multiple sources of data used in practice, including research evidence, client perspectives and experience, moment-by-moment process observation, and client feedback regarding progress towards specific, desired outcomes. We move beyond current debates purporting one framework over another to propose a synthesizing framework that situates evidence-based practice, empirically supported interventions and common elements/mapping and adapting practice within a common factors scaffolding framework. This framework provides a way for social workers to effectively make sound judgments using research and client data within the demands of contemporary practice. The article provides a brief overview of the four practice approaches followed by the proposed scaffolding framework and rationale, and concludes with implications for practice, professional education, and research.
Keywords: Common elements; Common factors; Empirically supported interventions; Empirically supported treatments; Evidence-based practice; Research evidence; dept.swk

The effects of cumulative risk and protection on problem behaviors for youth in an urban school-based system of care - Whitson, Melissa L.; Bernard, Stanley; Kaufman, Joy S. (Community Mental Health Journal, 2013)
The present study examined the cumulative effects of risk and protective factors on internalizing and externalizing problems for a sample of youth who were diagnosed with a severe emotional disturbance and enrolled in an urban school-based system of care. The sample included 139 Latino and African American children (ages 5-19; 65 % male) and their families. After controlling for demographic variables, the results of hierarchical multiple regression analyses revealed that cumulative risk and protection were significantly related to internalizing problem behaviors, and cumulative protection was negatively related to externalizing problem behaviors. The findings support the importance of including or increasing strength building approaches, in addition to risk reduction, in order to maximize prevention and intervention efforts for system-of-care populations.
Keywords: Affective Symptoms; African American; African Americans; Child; Child, Preschool; Children's mental health; Cumulative protective factors; Cumulative risk factors; Female; Hispanic; Hispanic Americans; Humans; Internal-External Control; Internalizing and externalizing behavioral problems; Interviews as Topic; Male; Psychiatric Status Rating Scales; Questionnaires; Regression Analysis; Risk; Risk Factors; School Health Services; Schools; Severity of Illness Index; Social Behavior Disorders; Socioeconomic Factors; Systems of care; Urban Population; antisocial personality disorder; article; child; control; dept.swk; emotional disorder; female; human; interview; male; organization and management; peer-reviewed; preschool child; psychological aspect; psychological rating scale; questionnaire; regression analysis; risk; risk factor; school; school health service; severity of illness index; socioeconomics; statistics; urban population

Relationships between child emotional and behavioral symptoms and caregiver strain and parenting stress - Vaughan, Ellen L.; Feinn, Richard; Bernard, Stanley; Brereton, Maria; Kaufman, Joy S. (Journal of Family Issues, 2013)
Children with emotional and behavioral disturbance often have difficulties in multiple symptom domains. This study investigates the relationships between child symptoms and caregiver strain and parenting stress among 177 youth and their caregivers participating in a school-based system of care. Youth were grouped by symptom domain and included those with low scores on both internalizing and externalizing symptoms, those with only high internalizing symptoms, those with only high externalizing symptoms, and those with high symptoms levels in both internalizing and externalizing domains. Results revealed significant group differences on measures of caregiver strain and parenting stress. Caregivers of youth with symptoms in both internalizing and externalizing domains reported the highest levels of strain and stress; however, there was some variation in group differences by caregiver outcome. The results of this study emphasize the importance of providing not only services for youth but also support services for their caregivers.
Keywords: caregiver strain; dept.swk; parenting stress; peer-reviewed; serious emotional and behavioral disturbance

From direct service to director of field education - Michaelsen, Diane (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2013)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Cultivating curiosity: integrating hybrid teaching in courses in human behavior in the social environment - Rodriguez-Keyes, Elizabeth; Schneider, Dana A (Journal of Teaching in Social Work, 2013)
This study illustrates an experience of implementing a hybrid model for teaching human behavior in the social environment in an urban university setting. Developing a hybrid model in a BSW program arose out of a desire to reach students in a different way. Designed to promote curiosity and active learning, this particular hybrid model has students engage in weekly online activities between their weekly on-ground classes. This article reviews key pedagogical concerns and presents preliminary findings, including student feedback, instructor observations, and strategies for faculty interested in developing such courses. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: dept.swk; education; hybrid; online; peer-reviewed; social work; student perceptions; technology

Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk

The impact of a mental health crisis respite upon clients' symptom distress. - Rosen, Jonathan; O'Connell, Maria (Community mental health journal, 2013)
This study examined clients who were admitted to a mental health respite program in the first 3 months of 2011 in order to identify the ability of the program to reduce symptom distress and to explore related psychosocial factors. Participants were provided with self-report questionnaires that included measurements of demographics, mental health status, symptom severity, and program satisfaction. Results indicate a significant improvement in symptom distress (p < 0.05), mental health confidence (p < 0.1), and self-esteem (p < 0.05) from admission to discharge. No change was detected in largely external measurements.
Keywords: *Mental Disorders/pp [Physiopathology]; *Mental Disorders/th [Therapy]; Adult; Community Mental Health Services; Community mental health; Female; Hospital diversion; Humans; Male; Mental Disorders; Mental health respite; Middle Aged; Questionnaires; Surveys and Questionnaires; Symptom distress; United States; adult; article; dept.swk; evaluation study; female; human; male; mental disease; mental health service; middle aged; pathophysiology; peer-reviewed; questionnaire

Robert t. muller: trauma and the avoidant client: attachment-based strategies for healing - Schneider, Dana A. (Clinical Social Work Journal, 2012)
Keywords: dept.swk

Revitalizing the vision in supervision: supporting the supervisor in home-based therapy programs - Rodriguez-Keyes, Elizabeth; Gossart-Walker, Sandy; Rowland, Cecilia (Smith College Studies in Social Work, 2012)
Home-based programs provide a growing number of mental health and case-management services to high-risk children, adolescents, and their families. The clinical service providers who work directly with these children and families have varying degrees of education and practice experience as well as a range of different supervisory needs. Because of the daily challenges service providers face, they require support from competent, available supervisors. The professionals who supervise them often assume that responsibility with limited, if any, training in providing supervision. New and experienced supervisors alike often find themselves in positions for which they are ill prepared, without suitable training or administrative support. This article describes a supervision seminar developed for supervisors who supervise the clinicians who provide home-based services. The seminar provides training, support, consultation, and other forms of assistance to help supervisors adapt their clinical skills for use in their supervisory roles.
Keywords: clinical supervision; clinical supervisor; dept.swk; home-based therapy; supervision seminar

The miracle bearers: narratives of birthing women and implications for spiritually informed social work practice - Schneider, Dana A (Journal of Social Service Research, 2012)
Women's childbirth experiences are not widely researched in the social work literature. Therefore, the purpose of this study is to answer questions related to the child-birthing experience. One hundred and nineteen participants responded to a 26-item online questionnaire between April and June 2008, and their written narratives were analyzed using a grounded theory approach. Themes regarding the spiritual dimensions of childbirth emerged from the data and support current research demonstrating the importance of spirituality in women's lives and the meaningful and transformative nature of childbirth experiences. Implications for addressing spirituality in practice when working with childbearing women are explored. Future research that explores how spirituality may function as a protective factor for women with difficult pregnancies, births, and transitions to parenting is recommended.
Keywords: Childbirth; dept.swk; narratives; spirituality; transformation; women

From bumps in the road to the edge of chaos: The nature of change in adults - Keenan, Elizabeth King (Journal of Social Work, 2011)
This article explores the question of how human beings change, how change is constrained, and how change emerges out of and subsequently creates new forms of stability with adults. The emergence of Dynamic Systems Theories (DST) from developmental biology and neuroscience provide the tools to engage in such an understanding by attending to the issues of time, balance, influencing parameters (within person and sociocultural and material environments), and multiple adaptive and maladaptive pathways. DST provides the framework to understand the dynamic processes of bio-psychosocial factors that provide human beings with the stability and the flexibility to navigate the challenges and stressors of living. Complexity, the ability to experience inner continuity as one is changing, is a fluid balance that supports effective functioning. Findings: Key principles and concepts of DST describe multiple pathways of stability and change. A case example illustrates how DST helps social workers understand client experiences and responses to stressors, formulate initial and ongoing assessments, and monitor clients' participation in change activities. Application: Social workers seek to help people who experience an imbalance due to an inability to effectively respond to the negative impact of a stressor. By understanding the various pathways of balance and imbalance along the continuum of continuity to change, social workers can better understand how stressors are impacting specific clients, and subsequently the kinds of change that would best assist each client.
Keywords: change; complexity theory; dept.swk; dynamic systems theory; peer-reviewed; self-organization; stressors

German for travelers: A novel in 95 lessons - Rakfeldt, Jaak (Psychiatric Services, 2010)
Keywords: dept.swk

The Roots of the Recovery Movement in Psychiatry - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (John Wiley & Sons, Ltd, 2010)
lessons learned from previous efforts with the goal of "getting it right" this time. In response to the common refrain that we know about and 'do' recovery already, the authors set the recovery movement within the conceptual framework of major thinkers and achievers in the history of psychiatry, such as Philippe Pinel, Dorothea Dix, Adolf Meyer, Harry Stack Sullivan, and Franco Basaglia. The book reaches beyond the usual boundaries of psychiatry to incorporate lessons from related fields, such as psychology, sociology, social welfare, philosophy, political economic theory, and civil rights. From Jane Addams and the Settlement House movement to Martin Luther King, Jr., and Gilles Deleuze, this book identifies the less well-known and less visible dimensions of the recovery concept and movement that underlie concrete clinical practice. In addition, the authors highlight the limitations of previous efforts to reform and transform mental health practice, such as the de-institutionalization movement begun in the 1950s, in the hope that the field will not have to repeat these same mistakes. Their thoughtful analysis and valuable advice will benefit people in recovery, their loved ones, the practitioners who serve them, and society at large. Foreword by Fred Frese, Founder of the Community and State Hospital Section of the American Psychological Association and past president of the National Mental Health Consumers' Association. © 2010 John Wiley & Sons, Ltd.
Keywords: dept.swk

The common factors model: implications for transtheoretical clinical social work practice. - Cameron, Mark; Keenan, Elizabeth King (Social Work, 2010)
Direct practice social workers today are challenged to address the requirements of the complex array of professional, organizational, institutional, and regulatory demands placed on them in the broader socioeconomic context of fewer resources and diminished public support for social welfare services in the United States. The common factors model provides an accessible, transtheoretical, empirically supported conceptual foundation for practice that may help to resolve this conundrum and support effective practice. Common factors are conditions and processes activated and facilitated by strategies and skills that positively influence practice outcomes across a range ofpractice theories. The model provides an expanded conceptualization of the "active ingredients" required for change to include a focus on conditions and processes as well as practice strategies and to focus on all who are involved in the work. The model is described and implications for practice are discussed.
Keywords: *Models, Theoretical; *Social Work/mt [Methods]; Change; Common factors; Empirical; Humans; Professional-Patient Relations; Social Support; Social work practice; Transtheoretical; dept.swk

Agency as the basis for transformation - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

Closing the hospital - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

Reciprocity in community‐based care - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

The everyday and interpersonal context of recovery - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

The rights and responsibilities of citizenship - Davidson, Larry; Rakfeldt, Jaak; Strauss, John (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

FromTraitement moral to moral treatment - Davidson, Larry; Rakfeldt, Jaak; Strauss, John S (The Roots of the Recovery Movement in Psychiatry: Lessons Learned, 2010)
Keywords: dept.swk

Navigating the ethical terrain of spiritually focused psychotherapy goals: multiple worldviews, affective triggers, and personal practices - Keenan, Elizabeth King (Smith College Studies in Social Work, 2010)
Constructing mutual, spiritually focused psychotherapy goals is a practice activity fraught with numerous ethical and countertransferential challenges. This article seeks to inform the thinking and enhance the ability of clinical social workers to engage in collaborative and responsive dialogues with their clients regarding the goals of spiritually focused clinical practice by (1) identifying the multiple value frameworks that influence decisions regarding practice goals, (2) articulating some of the ethical complexities and common countertransferential reactions associated with goal setting, and (3) providing self-reflection questions and guides to help therapists navigate the complexities of this material.
Keywords: Countertransference; Ethics; Goals; Piritually focused psychotherapy; dept.swk

Seeing the forest and the trees: using dynamic systems theory to understand “Stress and coping” and “Trauma and resilience” - Keenan, Elizabeth King (Journal of Human Behavior in The Social Environment, 2010)
Although research is beginning to capture the complex interactions of biopsychosocial variables operating within experiences of stressors and trauma, the bodies of research have remained largely separate and limited. This study describes a scaffold of factors and pathways based on principles from dynamic systems theories (DST) to organize the literatures on stress and coping and trauma and resilience. As a process model, DST provides the language to understand both impact and response to stressors and trauma: Not as a list of symptoms but as interactive processes within persons and between persons and their surroundings. © Taylor & Francis Group, LLC.
Keywords: Complexity theory; Dynamic systems theory; Stress and coping; Trauma and resilience; dept.swk; peer-reviewed

Substance abuse prevention: perspectives from india’s addiction treatment professionals - Perumbilly, Sebastian A; Anderson, Stephen A (American Journal of Sociology, 2015)
Keywords: dept.mft; peer-reviewed

Management and Leadership in Social Work: A Competency Based Approach - Rofuth, Todd W.; Piepenbring, Julie M. (Springer Publishing Company, LLC, Springer Publishing Company, 2019)
The authors have had many years of leadership and management experience in a variety of settings and have discovered that there are few books that cover the majority of topics related to leadership and management specifically for social work education and practice. This book covers all the main areas of expertise required in a typical social work leadership and management experience. It incorporates all 21 competencies and 126 practice behaviors from the Network on Social Work Management (NSWM) and nine competencies and 29 practice behaviors espoused by the Council on Social Work Education (CSWE) and can serve as a textbook for social work programs at the graduate level. The book has many unique features. It provides a comprehensive list of leadership and management competencies from the NSWM and the CSWE along with a list of competencies and practice behaviors. The book presents leadership and management competencies and practice behaviors each chapter along with cases, examples, and activities of how to use them in practice situations. It discusses in detail the differences between management and leadership along with best management and leadership practices. The book provides examples of how to motive and successfully work with different age cohorts. It presents effective communication and marketing strategies. The book discusses in detail how to effectively work with groups and give examples of how to make meetings productive. It exhibits specific problem-solving and decision-making strategies along with examples. The book summarizes how to manage a range of organizational functions. It discusses the importance of collaborating with community groups and other stakeholders to succeed in making a difference. The book contains five parts that replicate the <abbrev>NSWM</abbrev>’s four domains of leadership: executive leadership in social work; resources management practices; strategic management and administrative skills for organizational growth and success; community collaboration; and supplemental materials.
Keywords: Leadership; Vocational qualifications; Social Work; dept.swk; faculty_collection; methods; Efficiency, Organizational; organization & administration; Leadership; Professional Competence; Personnel Management

Build the social justice bridge: participatory photography with the international group work community - Gardella, L.G.; Prinsloo, R. (Social Work with Groups, 2021)
“Build the Social Justice Bridge” was a participatory photography project that engaged international group workers in an assessment of group work as a social justice profession. Inspired by principles of photovoice research, the project invited social work students, educators, and practitioners from around the world to contribute photographs and brief narratives that represented the relationship between group work and social justice. The photographs were exhibited during the opening session of the 2018 Symposium of the International Association for Social Work with Groups (IASWG) in South Africa, where more than 200 participants from ten countries reflected on the meaning of the photos for the group work community. In viewing the photos, symposium participants identified a common vision of social justice as well as culturally-specific approaches to group work. Implications are drawn for the internationalization of professional knowledge. © 2019 Taylor & Francis Group, LLC.
Keywords: South Africa; adult; article; dept.swk; female; human; human experiment; major clinical study; male; narrative; peer-reviewed; photography; physician; professional knowledge; social justice; social work student; vision; worker

Sexual Identity Development and Heteronormativity - Harvey, Rebecca; Stone-Fish, Linda; Levatino, Paul (The Handbook of Systemic Family Therapy, 2020)
Sexual identity development has traditionally been theorized about from within heteronormative societies founded on patriarchal notions with links to misogyny, racism, and classism, among others. These forms of domination have constrained the way sexual identity has been conceived of, researched and written about within the mental health fields and limited the efficacy of clinical work with all people but especially sexual minorities and those who are gender non-binary. In this chapter the authors will deconstruct heteronormativity, examine the deleterious effect of it on mental health, and locate the influence of intersections of oppression on the field of SFT theory and in clinical work. An LGBTQI (lesbian, gay, bisexual, transgender, questioning, intersex) affirmative clinical framework developed from systems theory and queer theory will be outlined, and then a case study using the framework will be described.
Keywords: LGBTQI; dept.mft; dept.swk; family therapy; heteronormativity; marriage and family therapy; sexual identity; systemic family therapy

Grief, loss and bereavement: An integrated perspective - Counselman-Carpenter, Elisabeth (Clinical social work practice, 2020)
Keywords: dept.swk

Teaching note—Taking social work undergraduates inside: the inside-out prison exchange program - Smoyer, Amy B. (Journal of Social Work Education, 2020)
The Inside-Out Prison Exchange Program is an experiential learning program that involves teaching college courses inside correctional facilitates to classes that include incarcerated and nonincarcerated students. This teaching note describes the program and argues that its congruence with social work values makes it a valuable tool for preparing students to take on social justice work. The impact of the program’s pedagogy and structure on students’ and faculty’s capacity for critical thinking and self-reflection is described. Logistical issues to consider in developing programs are discussed.
Keywords: article; critical thinking; dept.swk; human; human experiment; pedagogics; peer-reviewed; prison; program impact; social work; teaching

Food in correctional facilities: A scoping review - Smoyer, Amy B. (Appetite, 2019)
In the last 20 years, there has been an exponential increase in research about food in prison. Given this growing interest, it is appropriate to take stock of the field by mapping and synthesizing existing knowledge in order to identify gaps in knowledge and make recommendations for future research. Specifically, the purpose of this scoping review is to understand the experiences of incarcerated people with food in order to inform interventions that will promote positive outcomes for justice-involved individuals and correctional facilities. This review identified 38 peer-reviewed research articles about food in correctional facilities. This sample included qualitative (n = 28) and quantitative (n = 10) research that explored the both the pragmatic and symbolic dimensions of food in these settings. Taken together, this body of research provides a rich description of prison food practices and the implications of these practices on medical, psychological, and sociological outcomes. Moving forward, collaboration between academics, incarcerated people, and correctional practitioners is encouraged in order to develop programs that use this research to improve individual and intuitional outcomes. In addition, while emerging research has begun to develop knowledge about prison food in developing countries, the literature focuses primarily on the US, Canada and Western Europe and there is a need to expand the geographic scope of this inquiry.
Keywords: *Food Services; *Prisons; Canada; Consumer Behavior; Europe; Food Services; Humans; Nutritive Value; Prisons; United States; Western Europe; adult; article; catering service; clinical article; consumer attitude; dept.swk; developing country; female; human; justice; male; nutritional value; peer-reviewed; physician; prison

Hygge: Food and the construction of safety among incarcerated women in Denmark - Smoyer, Amy B.; Minke, Linda Kjær (Appetite, 2019)
Knowledge about women's socio-emotional experience of incarceration is sparse. To address this gap in the research, open-ended interviews were conducted with 9 incarcerated women in Denmark. The inquiry focused on their experiences with prison food and eating, including questions about hygge-related practices. Hygge is a cherished part of Danish culture that encourages people to create cozy environments by sharing food and fellowship. While this warm and comforting practice may seem incongruent with prison, contemporary theory about carceral geography suggests a wide range of emotional spaces within prisons and identifies the central role of incarcerated people and external norms on constructing these spaces. The participants’ narratives describe and explain the role of hygge in Danish prisons. Participants report using food and other props to construct hygge in their cells, in common areas, and with visitors, in order to build safety and manage the harshness of prison life. While these experiences are fleeting, findings suggest that the ability of these women to engage in hygge practices has a deeply positive impact on their lived experience of incarceration. The findings expand understanding about the role of food in prison and inform the practices of correctional facilities.
Keywords: dept.swk; peer-reviewed

Social determinants of health: the how, who, and where screenings are occurring; a systematic review - O’Brien, Kyle H. (Social Work in Health Care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one’s health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice. © 2019, © 2019 Taylor & Francis.
Keywords: Food Supply; Health Literacy; Health Services Accessibility; Health Status Indicators; Housing; Humans; Poverty; Social Determinants of Health; Social determinants of health; catering service; dept.hls; dept.rec; dept.swk; health care; health care delivery; health literacy; health status indicator; housing; human; integrated care; interprofessional practice; peer-reviewed; poverty; primary care; screening tools; social determinants of health

Voices should be heard: what personal stories of homelessness teach us about practice - Schneider, Dana A.; Cretella, Jill; Ranaudo, Sarah; Constantino, Daniel; Cota, Catherine F. (Families in society-The journal of contemporary social services, 2019)
The Voices Should Be Heard community-based participatory research project provided a platform for individuals experiencing homelessness to share their life stories and experiences. Participants offered their reflections on the oppression of homelessness and how the service delivery system could be improved. This article synthesizes these reflections and offers recommendations for practice aimed at reducing the oppression of homelessness and promoting social change. Using a strengths-based perspective, we offer points of entry for working with individuals experiencing homelessness.
Keywords: client-worker relationship; client–worker relationship; dept.swk; homelessness and housing; methods and analytics; modes of practice; peer-reviewed; professional issues; qualitative research; strengths-based practice; subjects of practice; working alliance

Hope, courage, and resilience in the lives of transgender women of color - Ruff, Nadine; Smoyer, Amy; Breny, Jean (The Qualitative Report, 2019)
There is a lack of qualitative and strengths-based knowledge about the lived experience of transgender women of color in the US. To address this research gap, a Photovoice project was undertaken with five transgender women living in a small urban area. Thematic analysis of the participants' discussion of their photographs identified three major themes: Hope, courage, and resilience. Analysis suggests a framework for understanding these women's lived experiences and the psychosocial tools that they use to negotiate their daily lives and persevere in the face of interpersonal and structural oppression. © 2019 Nova Southeastern University. All rights reserved.
Keywords: Courage; Hope; Photovoice; Resilience; Transgender Women; Women of Color; dept.pch; dept.swk; peer-reviewed; ⛔ No DOI found

Understanding the role of the brick-and-mortar classroom in course design and implementation of the “flipped” classroom: An exploratory case study - Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Teaching and Learning with Technology, 2019)
Keywords: dept.swk; peer-reviewed

The Arc of Justice: Examining Policies and Laws to Advance the Human Rights of Transgender and Gender Expansive Children - Redcay, Alex; Counselman-Carpenter, Elisabeth; McMahon, Sheila; Luquet, Wade; Rice, Karen; Lance, Roseanna (Journal of Human Rights and Social Work, 2019)
The role of the social worker in the achievement of human rights is to assist individuals in their struggle for dignity and their attainment of their full potential. Ethical social work ensures just laws and practices that allow all persons to live without discrimination. The purpose of this paper is to present the practice and policy implications of the last five years of court cases regarding transgender and gender expansive (TGE) children and school systems in the USA. This paper outlines the legal justifications for revisions to the current procedures and policies of interacting with TGE children, including use of restrooms consistent with gender identity (RCGI). These recommended guidelines are designed to prevent ongoing human rights violations and create pathways for TGE children to live their lives congruently with their gender identity. Basic human rights for the TGE individual include policy improvements involving restrooms, locker rooms, showers, overnight accommodation, affirmed name, and identification for the child welfare, mental health, educational, medical, juvenile justice, and law enforcement systems. © 2019, Springer Nature Switzerland AG.
Keywords: Ethics; Gender expansive children and youth; Policy; Transgender; dept.swk; peer-reviewed

Provider Attitudes, Organizational Readiness for Change, and Uptake of Research Supported Treatment - Bornheimer, Lindsay A.; Acri, Mary; Parchment, Tyrone; McKay, Mary M. (Research on Social Work Practice, 2019)
Purpose:As implementation and evaluation of research supported treatment (RST) expands across diverse mental health settings, it is essential to understand the facilitators and inhibitors of uptake. The current study examined the relationships between organizational readiness for change, attitudes toward RST, and use of RST among a sample primarily of social workers.Methods:Participants included 158 providers from public child mental health outpatient clinics in the New York metropolitan area. Data were analyzed using structural equation modeling.Results:Use of RST was greater among providers who were younger and had fewer years of professional experience. Both organizational need for change and climate directly and indirectly related to use of RST through attitudes toward RST (partial mediator).Discussion:The organizational context is an important factor that relates to attitudes toward and use of RST in practice. Future research is needed to continue examining factors of RST uptake and sustainability.
Keywords: dept.swk; organizational readiness for change; provider attitudes; research supported treatment; treatment uptake

Teaching note—MSW student perceptions of learning advanced clinical practice skills through the flipped classroom - Counselman-Carpenter, Elisabeth A. (Journal of Social Work Education, 2019)
The flipped classroom, with its focus on student-centered learning and active student engagement, is a growing trend in social work education. This article presents an innovative way of delivering practice content through the flipped classroom model, which can be adapted for any level of social work education. It walks readers through the steps of developing the course and the successes and challenges of the flip, particularly with an incorporated skills lab component. Additionally, this article shares student reflections on the development and execution of the course, with specific feedback on the experiential learning environment, discussions surrounding instructor workload and preparation, and implications for future iterations of the course from students who had very little prior technologically centered learning experiences.
Keywords: dept.swk; peer-reviewed

Older adults’ lived experience of incarceration - Smoyer, Amy B.; Madera, Johanna Elumn; Blankenship, Kim M. (Journal of Offender Rehabilitation, 2019)
This qualitative analysis explores older adults’ lived experiences of incarceration. As part of a larger mixed-methods longitudinal study, 23 older adults were interviewed about their prison and reentry experiences. Findings describe experiences of loss, lack of medical attention, abuse by staff and other inmates, and the uncertainties and danger of prison life. After release, participants reported experiencing anxiety and stress related to their prison experiences. While participants reported that the ability to manage prison life deteriorated with age, some benefits of their senior status were also described. Maturity may allow older prisoners to remove themselves from volatile situations. Participants described experiences of rest and recovery, reflecting coping mechanism and resilience that could improve psychosocial outcomes during and after prison. This descriptive analysis centers the voices of older prisoners and informs interventions to support this vulnerable community.
Keywords: Prison; dept.swk; incarceration; older people; peer-reviewed; qualitative; reentry

Prepared to care: an exploration of continuing education trends of nurses caring for injured children - Roney, Linda Nancy; Acri, Mary C. (Journal of Trauma Nursing, 2019)
The significance of nursing competence in the care of pediatric trauma patients has been well documented. Continuing education for trauma nurses is a critical component of maintaining competence in pediatric trauma care; yet, there is significant variability in the programs and resources used to support this goal. The purpose of this current study was to describe the educational activities that practicing registered nurses engage in to inform their care of injured children. A quantitative, descriptive nonexperimental research design was utilized to describe the educational programs that members of the Society of Trauma Nurses (STN) must complete to work in verified and designated trauma centers. Participants completed a survey instrument that included demographic questions, pediatric trauma educational programs required/offered by their employer, and feedback about pediatric trauma nursing education. A total of 266 STN members completed the electronic survey, reflecting a 9% response rate. Most of the participants reported that the verifying body required trauma nursing education hours (n = 187, 70.3%). The number of required courses ranged from 1 to 6, with 33 (12.4%) reporting this 3-course combination-emergency nursing pediatric course (ENPC), pediatric advanced life support (PALS), and trauma nursing core course (TNCC). The second most common combination of courses (n = 30; 11.3%) was required to take both PALS and TNCC. No significant relationship was found between verifying agency type and continuing education program required (p¿ .05). Trauma nursing core course was the most popular course (n = 208; 79%), followed by PALS (n = 194; 73%) and ENPC (n = 103; 38%). Participants also shared barriers to continuing education activities. It has been 10 years since pediatric trauma nursing course utilization was first explored in the literature. There continue to be significant opportunities to support nurses in continuing education activities related to the care of injured children. While barriers to accessing these types of activities sometimes exist, it is the responsibility of the pediatric trauma community to explore these challenges even further and collaborate with others interested in improving the care of injured children.
Keywords: Child; Child Health Services; Clinical Competence; Education, Nursing, Continuing; Emergency Nursing; Female; Humans; Male; Nursing Staff, Hospital; Pediatric Nursing; Pediatric trauma; Pediatric trauma nursing; Surveys and Questionnaires; Trauma education; Trauma verification; child; child health care; clinical competence; dept.swk; education; emergency nursing; female; human; male; nursing education; nursing staff; pediatric nursing; peer-reviewed; questionnaire

Crowdsourced social work educator technology standards - Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Applying accessibility practices across a curriculum - Marquart, M; Counselman-Carpenter, E (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Case study – teaching online with students who are deaf - Marquart, M; Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Louis Lowy - Sozialarbeit unter extremen Bedingungen: Lehren aus dem Holocaust - Gardella, Lorrie Greenhouse (Lambertus-Verlag, 2019)
Keywords: dept.swk

Repair the world: Group work in the Deggendorf Displaced Persons Center, 1945-1946 - Gardella, Lorrie Greenhouse (Groupwork, 2019)
This paper explores the formation of a transitory community in the UNRRA Displaced Persons Center in Deggendorf, Germany, where Jewish Holocaust survivors used social group work to preserve their past, to restore humane values, and to prepare for new lives.  Social activism through task groups and activity groups affirmed individual and community self-determination while promoting recovery from trauma.  The experience of the She’erith Hapleitah or “surviving remnant,” as they called themselves, though historically specific, has implications for group work with migrants today.
Keywords: Citizenship; Groupwork; Holocaust survivors; Hope; Migrants; Recovery; Refugees; dept.swk; peer-reviewed

The impact of fluid attraction and fluid identity on mental health - Redcay, Alex; Counselman-Carpenter, Elisabeth; Proctor, Curtis (Journal of Gay & Lesbian Mental Health, 2019)
Using data from the National Longitudinal Study of Adolescent Health, this study examined the impact of sexuality factors and satisfaction with partner on stress, anxiety, and depressive symptoms. Multiple regression was used to evaluate the impact of predictors such as sexuality factors and relationship satisfaction on the dependent variables: stress, anxiety, and depression. Three main results were discovered. First, sexual minority females who have lower levels of education and are dissatisfied with their relationship experience significantly higher stress, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or stress. Second, sexual minority females who have lower levels of education and who are dissatisfied with their relationship experience significantly higher anxiety, while sexual minority males do not differ from heterosexual males in terms of relationship satisfaction or anxiety. Finally, female sexual minorities who have lower levels of education reported fluid attraction, fluid identity, dissatisfaction with their relationship, and have significantly higher depression when compared to male sexual minorities or heterosexuals. Further research should examine gender and fluidity in greater detail. © 2018, © 2018 Taylor & Francis Group, LLC.
Keywords: Anxiety; depression; dept.swk; fluid attraction; fluid identity; peer-reviewed; satisfaction with partner; sexual orientation; stress

Examining the impact of psychological factors on hospital length of stay for burn survivors: A systematic review - O’Brien, Kyle H; Lushin, Victor (Journal of Burn Care & Research, 2019)
Recovery of burn patients may be impeded by mental health problems. By gaining a better understanding of the impact that psychological factors may have on hospital length of stay, providers may be better informed to address the complex needs of burn survivors through effective and efficient practices. This systematic review summarizes existing data on the adverse psychological factors for the length of burn patients' hospitalization, and assesses the methodological quality of the extant literature on mental health conditions of burn survivors. A literature search was conducted in four electronic databases: PubMed, PsychINFO, Science Direct, and the Cumulative Index to Nursing and Allied Health Literature. Results yielded reports published between 1980 and 2016. Methodological quality was assessed by using an 11-item methodological quality score system. Seventy-four studies were identified by search; 19 articles were eligible for analysis. Findings demonstrate paucity of evidence in the area. Reports indicate longer hospital stay among burn patients with mental health problems. Substance use was the most consistent mental-health predictor of longer hospital stay. Heterogeneity in data on mental health conditions rendered impossible estimation of effect sizes of individual psychological factors on length of hospitalization. Many studies over-relied on retrospective designs, and crude indicators of psychological factors. Findings indicate that mental health problems do have an impact on the trajectory of burn recovery by increasing the length of hospital stay for burn survivors. Inpatient mental health services for burn patients are critically needed. Prospective designs, and more sensitive psychological indicators are needed for future studies.
Keywords: Article; Burns; Hospitalization; Humans; Length of Stay; Survivors; burn; burn patient; burn survivor; dept.hls; dept.rec; dept.swk; distress syndrome; hospitalization; human; length of stay; mental disease; mental health; peer-reviewed; psychological aspect; psychology; substance use; survivor; systematic review

Realizing the potential for leadership in social work - Keenan, Elizabeth King; Sandoval, Silvia; Limone, Christine (Journal of Social Work, 2019)
Ongoing racism, structural inequity, dehumanizing institutional bureaucracies, unresponsive service delivery systems, and gaps in services for emerging needs are just some of the pervasive challenges in need of social work leadership. The multidisciplinary nature of social work practice also requires value-based leadership processes on multiple ecological levels to address the challenges inherent within social delivery systems. Social work encourages all social workers to lead these change efforts, but research on front-line social work leadership is lacking. Constructionist conceptualizations of leadership as social influence processes provide a unit of analysis to examine front-line leadership. A secondary analysis of qualitative data examining social work practice that promotes well-being and social justice revealed leadership processes in multiple social work practice settings. Findings Front-line social workers demonstrate three overarching leadership processes in their practice: challenging injustice and changing mindsets, conduit for change, and organizing resources and relationships. Applications Conceptualizing leadership as social influence processes identifies and acknowledges the leadership of front-line social workers, expanding the profession's capacity to collectively articulate and initiate change with a range of social problems and systemic challenges in organizations and communities.
Keywords: Social work; article; dept.swk; health care delivery; human; leadership; occupation; peer-reviewed; qualitative research; racism; secondary analysis; social constructionism; social justice; social work; social work practice; wellbeing

The Positive Assessment: A Model for Integrating Well-Being and Strengths-Based Approaches into the Child and Adolescent Psychiatry Clinical Evaluation. - Schlechter, Alan Daniel; O'Brien, Kyle H; Stewart, Colin (Child and adolescent psychiatric clinics of North America, 2019)
In traditional medical practice, the diagnostic interview is focused on symptom collection, diagnosis, and treatment. The psychiatric interview is based on the medical model, but mental health clinicians lack the tests found in general medicine. Rapport is the most essential tool for the psychiatrist to uncover symptoms and develop a diagnosis and treatment plan. This article brings a scientific lens to the psychiatric interview. Under this microscope the value of eliciting the patient's well-being at the outset of the interview becomes clear. Using positive psychology, an evidenced-based rationale for the positive assessment is outlined and methodology and practice of the assessment reviewed. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Adolescent Psychiatry; *Child Psychiatry; *Child Welfare; *Mental Disorders/di [Diagnosis]; Adolescent; Adolescent Psychiatry; Assessment; Caregivers; Child; Child Psychiatry; Child Welfare; Common factors theory; Diagnostic interview; Humans; Mental Disorders; Neurosciences; Positive emotions; Positive psychology; Psychiatry; Psychiatry interview; Rapport; Review; Well-being; achievement; adolescent; caregiver; child; child psychiatry; child welfare; clinical evaluation; dept.hls; dept.swk; doctor patient relationship; emotion; human; mental capacity; mental disease; mental health; motivational interviewing; neuroscience; patient assessment; peer-reviewed; priority journal; psychiatry; psychological interview; psychological well-being; reward; social life

Self care - Counselman-Carpenter, Elisabeth (Working with grief & traumatic loss: Theory, practice, personal reflection and self-care for clinicians, 2019)
Keywords: dept.swk

Remembering Jim Garland: Loneliness in the group - Gardella, Lorrie Greenhouse (Group work: Creating space for all voices, 2019)
Keywords: dept.swk

“My sister is the one that made me stay above water”: How social supports are maintained and strained when survivors of intimate partner violence reside in emergency shelter programs - Stylianou, Amanda M.; Counselman-Carpenter, Elisabeth; Redcay, Alex (Journal of Interpersonal Violence, 2018)
While social support is critical in helping intimate partner violence (IPV) survivors heal and build hope, social isolation is a frequent experience for survivors. For survivors residing in domestic violence (DV) emergency shelters, the isolation from social supports is often exacerbated by shelter rules and policies. This study uses a 20th century feminist framework to understand the ways in which social support networks are maintained and/or strained when survivors reside in DV emergency shelters. Among this sample of 76 survivors, 40 participants identified family members as their support system, with siblings and mothers most frequently identified, and 14 participants identified friends as their social support. Prior to entering the DV shelter, survivors reported that their support networks provided encouragement and motivation along with emotional support, financial and material support, and support with children. Participants spoke about the process of informing their support systems of the transition into a DV shelter, the positive and negative impacts of the transition on their support system, and the roles that frequent telephone calls and texts played in maintaining their support networks. Participants reported positive impacts of residing in a DV shelter including improved emotional and physical health, strengthened emotional relationships, and improved physical and emotional resource provision. For those participants reporting negative experiences, they frequently identified logistical barriers, including the inability to receive visitors at the shelter, the distance between them and their friends and family, and strict rules around curfew and child care. Our findings invite researchers and practitioners to consider further examination of best practices around programming that supports survivors in maintaining social supports while residing in shelter programs
Keywords: dept.swk; peer-reviewed

Welcome the stranger: Group work and hospitality in a fearful era - Gardella, Lorrie Greenhouse (Group work around the globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk

Facilitators and barriers in treatment seeking for substance use disorders: indian clinical perspectives - Perumbilly, Sebastian A.; Melendez-Rhodes, Tatiana; Anderson, Stephen A. (Alcoholism Treatment Quarterly, 2018)
Despite great advances that have been made in the understanding and treatment of substance use disorders (SUDs), fewer than 11% of eligible patients seek treatment. Few studies have explored the roles of facilitators and barriers in treatment seeking from the perspectives of addiction-focused clinicians working in developing countries. This descriptive study used a mixed-methods research design with concurrent strategies. Research participants were addiction-focused clinicians (N = 112) working in India. Primary research questions examined (1) key facilitators that motivate patients to seek treatment, (2) major barriers in treatment seeking, and (3) critical strategies for enhancing treatment seeking with the support of family, friends, and community. Key facilitators of treatment seeking included informed and caring family members, friends, and community. The most common barriers were patients’ denial of the problem of SUDs, shame in admitting the problem, and belief and confidence that they can quit using substances by themselves anytime. A systemically focused public awareness creation strategy, implemented simultaneously at various key sectors in society, was recommended for facilitating treatment seeking and removing barriers. Implications for clinicians, patients, public health personnel, community leaders, and regional, national, and global policy makers are reviewed. © 2018, © 2018 Taylor & Francis.
Keywords: Addiction treatment; Article; India; adult; aged; awareness; barriers to treatment; clinician; community; dept.mft; drug dependence; facilitators of treatment; female; help seeking behavior; human; male; peer-reviewed; social stigma; substance use disorders; treatment seeking

Retooling the health care workforce in the era of the Affordable Care Act: An evaluation of an advanced certificate program in integrated primary and behavioral health care - O’Brien, Kyle H.; Acri, Mary C.; Campanelli, Peter C.; Cerniglia, Joseph A.; McKay, Mary M. (Journal of Teaching in Social Work, 2018)
The Affordable Care Act aims to increase affordable coverage, reduce overall costs, and improve health outcomes. To achieve these aims, new knowledge and skills must be built within the existing workforce. The purpose of this article is to examine the behavioral and organizational changes brought about by an educational program that aimed to retool the healthcare workforce for the implementation of integrated primary and behavioral healthcare models, with an added emphasis on prevention. Sixty-three participants of an Advanced Certificate Program completed 1 or more evidence-informed learning modules centered on integrated primary and behavioral health care. The vast majority of students who completed each of the 5 modules of the program reported acquiring new knowledge and skills. Student satisfaction of the program met or exceeded overall expectations. In addition, program participation has resulted in not only students’ intentions to change workplace practices but also actual implementation of workplace changes related to integrated care models. The Advanced Certificate Program appears to be a promising platform for service providers to align their knowledge and skills with the premises of current healthcare reform. © 2018, © 2018 Taylor & Francis.
Keywords: Affordable Care Act; Integrated primary and behavioral health care; certificate programs; dept.rec; dept.swk; integrated care; peer-reviewed; workforce training

An Examination of the Relationship between Maternal Depression and Barriers to Child Mental Health Services - Acri, Mary C.; Bornheimer, Lindsay; Hamovitch, Emily; Lambert, Kate (Children and Youth Services Review, 2018)
Objective: Maternal depression is a common, chronic set of disorders associated with significant burden to caregivers, children and families. Some evidence suggests that depression is associated with perceptions of barriers to child mental health treatment and premature termination from services. However, this relationship has not yet been examined among a predominantly low-income sample, which is at disproportionately high risk of depression, child mental health problems, and treatment drop out. Accordingly, the purpose of this study is to examine the relationships between caregiver depression and perceived barriers to treatment. Methods: Three hundred twenty (n=320) children between the ages of 7 to 11 and their caregivers were assigned to either the 4 Rs and 2Ss for Strengthening Families, which is a multiple family group intervention, or services as usual (SAU) consisting of typical outpatient mental health services. Caregiver depression was measured by the Center for Epidemiologic Depression Scale; perceived barriers to treatment were assessed via the Kazdin Barriers to Treatment Scale. Results: Clinically significant levels of depressive symptoms at baseline were significantly associated with greater scores in all four barriers to treatment subscales (stressors and obstacles competing with treatment, treatment demands and issues, perceived relevance, relationship with therapist) at post-test. Conclusions: Addressing maternal mental health, and attending to stressors that impede poverty-impacted families from child services is critical for the health and functioning of caregivers, and to ensure that children with mental health problems receive treatment.
Keywords: dept.swk; peer-reviewed

Mining for Posttraumatic Growth (PTG) in Sexual Minority Women Who Survive Intimate Partner Violence: A Conceptual Perspective. - Counselman-Carpenter, Elisabeth; Redcay, Alex (Behavioral Sciences, 2018)
This theoretical paper explores the need to use posttraumatic growth (PTG) as a framework when studying sexual minority women (SMW) who are survivors of intimate partner violence (IPV) to examine the relationship between risk factors such as stress, anxiety and alcohol use and to understand the role of protective factors through mining for the presence of posttraumatic growth (PTG). Despite a call for continued research in this highly vulnerable population, representative studies of SMW and PTG remain extremely limited. Research that examines the relationship between IPV, behavioral health issues, and posttraumatic growth would provide the opportunity to develop tailored intervention models and opportunities for program development to decrease isolation and increase factors of posttraumatic growth. In particular, the impact of how interpersonal relationships as potential mediators and/or outcomes of posttraumatic growth (PTG) needs to be explored more thoroughly. PTG is a valuable framework for vulnerable populations such as sexual minority women because it focuses on how transformative change may result from traumatic experiences such as surviving IPV.
Keywords: Intimate partner violence; Post-traumatic growth; Sexual minority women; dept.swk; intimate partner violence; peer-reviewed; sexual minority women

Barriers and facilitators to mental health screening efforts for families in pediatric primary care - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O’Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M (Journal of Family Social Work, 2018)
The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions. © 2018, © 2018 Taylor & Francis.
Keywords: Screening and detection efforts; article; case report; child; child mental health; clinical article; dept.rec; dept.swk; female; human; human experiment; integrated care; male; mental health; outcome assessment; peer-reviewed; perception; poverty; primary medical care

From Values to Passion to Enlivened Practice: A Palette of Possibilities - Keenan, Elizabeth (Reflections: Narratives of Professional Helping, 2018)
This narrative offers a palette of possibilities for linking micro and macro practices that arose from interviews with social workers who were viewed as addressing the profession’s dual purpose of individual well-being and social justice in their practice. I begin with my own experiences and desires to link micro and macro together as a clinical social worker and community organizer. An interlude describing the way the social workers stretched my thinking comes in between the themes. I conclude with a final reflection on the impact of their stories and implications for future research and practice.
Keywords: Macro Practice; Micro Practice; Social Justice; Well-Being; dept.swk; macro practice; peer-reviewed; social justice; social work methods; social work practice; values; ⛔ No DOI found

Multiple family group service delivery model for children with disruptive behavior disorders: Impact on caregiver stress and depressive symptoms - Gopalan, Geetha; Bornheimer, Lindsay A.; Acri, Mary; Winters, Andrew; O’Brien, Kyle H.; Chacko, Anil (Journal of Emotional and Behavioral Disorders, 2018)
Disproportionately high rates of caregiver stress and depression are found among poverty-impacted communities, with high levels of caregiver stress and depression putting youth at heightened risk for the onset and perpetuation of disruptive behavior disorders. The purpose of this study was to examine the effects of a behavioral parent training program called the 4Rs and 2Ss for Strengthening Families Program (4R2S) on caregiver stress and depressive symptoms among 320 youth aged 7 to 11 and their families assigned to either the 4R2S or services as usual (SAU) condition. Among caregivers with clinically significant (CS) scores at baseline, 4R2S participants manifested significantly reduced scores on the stress and depressive symptom scores to SAU participants at 6-month follow-up. Findings suggest that 4R2S may reduce caregiver stress and depressive symptoms among those caregivers initially manifesting CS levels of stress or depressive symptoms.
Keywords: dept.rec; dept.swk; peer-reviewed

Stigma, housing and identity after prison. - Keene, Danya E; Smoyer, Amy B; Blankenship, Kim M (The Sociological review, 2018)
Existing research suggests that individuals who are released from prison face considerable challenges in obtaining access to safe, stable, and affordable places to live and call home. This article draws on repeated qualitative interviews (conducted every 6 months over a period of 3 years) with 44 formerly incarcerated individuals, to understand how these individuals experience the search for a home after their prison release. The interviews show that the quest for a home is central to participants' reintegration projects as they seek to establish themselves as 'decent' and economically self-sufficient citizens, and shed stigmatized identities associated with incarceration, poverty, homelessness, and place. Interviews also suggest that their quest for a home is an arduous one as they encounter numerous barriers to housing arising from both structural and interpersonal forms of incarceration stigma. Somewhat paradoxically, the challenges that they face in accessing housing seem to hinder their ability to shed the stigmatized identities associated with their incarceration. Ultimately, the narratives presented here show how stigma can restrict access to a valuable material and symbolic resource (housing), resulting in ongoing stigmatization, and contributing to the enduring and discrediting mark of incarceration. In this way, the study illustrates how stigma that is enacted by both individuals and the state, that is embodied in place, and that is internalized and managed by stigmatized individuals themselves, can work to reproduce power and serve as justification for inequality.
Keywords: Housing; Incarceration; Spatial stigma; dept.swk; peer-reviewed

Social work and hospitality: An oral history of Edith Stolzenberg - Gardella, Lorrie Greenhouse (Journal of Religion & Spirituality in Social Work: Social Thought, 2018)
Edith Richman Stolzenberg (1913–2004) was the first woman to be hired as a social worker in Hartford Public High School in Hartford, Connecticut. In a career that spanned 60 years and much of 20th-century social welfare history, she was motivated by the social justice tradition of her Jewish upbringing and the religious value of hospitality to advocate for children and families. As we enter a harsh new era for social services, this oral history explores the radical possibilities for integrating social work goals and religious values.
Keywords: adolescents; children; community; dept.swk; ethics; hospitality; oral history; religion; social work practice

An Examination of Peer-Delivered Parenting Skills Programs Across New York State - Acri, Mary C.; Craig, Nancy; Adler, Josh (Community Mental Health Journal, 2018)
Peers are an important adjunct to the public mental health service system, and are being increasingly utilized across the country as a cost-effective solution to workforce shortages. Despite the tremendous growth of peer-delivered support over the past two decades, it has only been within the past few years that peer programs have been the subject of empirical inquiry. The purpose of this study was to examine the prevalence and characteristics of peer-delivered parenting programs across the New York State public mental health service system. We surveyed 46 family peer organizations across New York State regarding their delivery of structured peer-delivered parenting programs. Thirty-four (76%) completed the questionnaire, and of them, 18 (53%) delivered a parenting program. Subsequent interviews with seven of the 18 organizations revealed peer organizations had been delivering eight unique parenting programs for upwards of two decades. Additionally, organizations offered multiple supports to families to participate. Training, supervision, and issues around fidelity are discussed, as well as the implications of this study for states utilizing a peer workforce.
Keywords: Adolescent; Behavior parent training programs; Child; Child, Preschool; Education, Nonprofessional; Humans; Infant; Infant, Newborn; Mental Health Services; New York; Parents; Peer Group; Peer support services; Peer-delivered family support; Surveys and Questionnaires; dept.swk; peer-reviewed

Couscous in Tilburg: Prison food narratives and the quality of prison life in a Belgian-Dutch prison - Vanhouche, An-Sofie; Smoyer, Amy B.; Minke, Linda Kjaer (Prison Service Journal, 2018)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Efficacy of the flipped classroom to teach play therapy: A mixed-methods study - Counselman-Carpenter, Elisabeth A. (International Journal of Play Therapy, 2018)
This mixed-methods study, including quantitative and qualitative measures, evaluated how a flipped classroom learning environment that included a hands-on experiential skills lab to teach play therapy improved student’s knowledge, attitude, and skills related to play therapy. Participating students (n = 18) completed the Play Therapy Knowledge, Attitudes, and Skills Survey (PTKASS) at the beginning and the end of the course. Students also reflected upon their experience in the skills lab each week in anonymous online feedback journals, which were analyzed at the conclusion of the semester for common themes by multiple coders. Students scores were significantly different on all subscales of the PTKASS: attitude (p = .0012), knowledge (p < .001), with the biggest growth in the skills subscale (p < .001). Through concurrent triangulation, these differences directly correlated to relevant qualitative themes that emerged from student feedback journals. The results of this study indicate strong support for the flipped classroom as an opportunity to develop graduate students’ knowledge, attitudes, and skills in play therapy. (PsycINFO Database Record (c) 2018 APA, all rights reserved)
Keywords: Classrooms; Clinical Practice; Play Therapy; Professional Development; Social Casework; Teaching Methods; dept.swk; peer-reviewed

You’ve got a friend. exploring the role of friendships in the lives of men 80 and over - Gesino, J (2018)
Keywords: dept.swk

Waiting for shelter: Perspectives on a homeless shelter's procedures - Brown, Molly; Mihelicova, Martina; Lyons, Jennifer; DeFonzo, Jennifer; Torello, Samantha; Carrion, Andres; Ponce, Allison N. (Journal of Community Psychology, 2017)
Research on homeless shelter implementation is limited. Some shelters have lengthy waitlists, which raises important questions about implications of waitlists for individuals with immediate shelter needs. This study used qualitative methods to understand the experiences of shelter seekers who were on a shelter waitlist (N = 59), including individuals who entered the shelter from the waitlist, and those removed from the shelter waitlist for procedural reasons. The average waitlist time was nearly 3 weeks, and 22.0% stayed at least one night on the street or another public place while on the waitlist. Responses to open-ended questions regarding barriers and effectiveness of the shelter referral procedures revealed 4 themes: procedural challenges, procedural benefits, benefits of the temporary stay, and communication challenges. Further research is needed to inform shelter implementation on a larger scale in accordance with current community-wide efforts to coordinate shelter services.
Keywords: dept.swk; female; human; major clinical study; male; night; patient referral; qualitative analysis

A woman doing life: Notes from a prison for women - Smoyer, Amy B. (Affilia-Journal of Women and Social Work, 2017)
Keywords: dept.swk

Development of the citizens measure into a tool to guide clinical practice and its utility for case managers - Bellamy, Chyrell; Kriegel, Liat; Barrenger, Stacey L.; Klimczak, Michele; Rakfeldt, Jaak; Benson, Victoria; Baker, Michaella; Benedict, Patricia; Williamson, Bridgett; MacIntyre, Gillian (American Journal of Psychiatric Rehabilitation, 2017)
A measure of citizenship was developed and validated by Rowe and colleagues (O’Connell, Clayton, & Rowe, 2017). The items clustered around the 5 Rs of citizenship as defined by Rowe et al.: relationships, rights, resources, roles, and rights, and a sense of belonging. Although a measure has its utility in clinical settings, to address time constraints and other administrative burdens expressed by providers in their day-to-day practice, a citizens tool was developed as a practical way that providers can enhance dialogue between providers and clients on citizenship for clients served in mental health and criminal justice reentry settings. This article describes the development of the tool, testing of the tool’s utility with case managers, and implications for practice. © 2017 Taylor & Francis.
Keywords: Article; adult; case management; case manager; citizenship; clinical practice; community inclusion; community integration; dept.swk; evidence based medicine; female; human; major clinical study; male; marginalized communities; mental capacity; mental disease; mental health service; poverty; practical clinical tools; priority journal; psychological well-being; self concept; social support; socioeconomics; translational research

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education--accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education, Nursing, Baccalaureate; Educational Status; Educational Technology -- Utilization; Faculty Development; Faculty Practice; Faculty, Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools, Nursing; Self-Efficacy; Socioeconomic Factors; Students, Nursing, Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Hungry on the inside: Prison food as concrete and symbolic punishment in a women’s prison - Smoyer, Amy B; Lopes, Giza (Punishment & Society, 2017)
Women’s perceptions of the prison experience and the punishing dimensions of their confinement are under-examined. To expand knowledge in this area, Sexton’s theory of penal consciousness is used to analyze formerly incarcerated women’s narratives about prison food. This analysis builds understanding about the lived experience of incarceration by explicating one dimension of prisoners’ understandings and perceptions of punishment. Women’s narratives describe both concrete and symbolic punishments associated with food. Participants spoke about poorly designed, sloppy food systems that left them feeling uncared for, ignored, frustrated, and humiliated. Women articulate experiences of hunger that reflect both a deprivation of adequate food and a rationing of humane attentions. These punishing perceptions may inhibit the efforts of social service and health providers to engage incarcerated and formerly incarcerated women in care. In contrast, exceptional participant narratives about positive, non-punishing food experiences suggest that ameliorated food systems could improve the lived experience of incarceration and promote the engagement in services that is needed to improve the outcomes of incarcerated and formerly incarcerated women.
Keywords: dept.swk; food; prison; punishment; women

“To feel him love me”: Emerging intersections of identity, queerness, and differing ability - Harvey, Rebecca (Gender, sex, and sexuality among contemporary youth, 2017)
AbstractOriginality/value This paper provides an alternative approach to nurturing queer identity by (1) creating refuge for emerging sexualities; (2) allowing for difficult dialogues where ability, sexuality, and gender can be pragmatically discussed, performed, and negotiated; (3) tolerating the discomfort of these difficult dialogues and pushing through to nurturing the unique queerness that evolves out of these conversations; and finally (4) encouraging transformation of all participants including client and practitioners. The practitioners discuss their own transformation through the co-created dialog with each other and with the client.
Keywords: Disability; Gay; Gay couple; Intersectionality; Queer; dept.mft; dept.swk

A "Just Sense of Well-Being": Social Work's Unifying Purpose in Action. - Keenan, Elizabeth King; Limone, Christine; Sandoval, Silvia L (Social work, 2017)
For over a century the social work profession has had a dual purpose, to promote both human well-being and social justice, but we have not found research that explores how social workers understand and work toward both purposes across multiple practice roles and settings. Authors of this article conducted qualitative research to examine how 18 social workers in various roles and settings understand and implement both purposes in their practice. Instead of a dual purpose, participants described a unifying purpose: a "just sense of well-being" that transcends role and setting. Valuing the dignity and worth of all human beings frames and fuels their work toward a just sense of well-being through three interactive themes: challenging injustice on every level; constructing justice through relationship and resource organizing; and constructing justice through the creation of accepting environments where professionals, clients, and community members can reflect and question, and change mind-sets and actions. Participants provided an array of possibilities for action with clients, professionals, and public leaders within organizations and communities. The implication here is that social workers are charged to reinvigorate purpose and values back into practice with value-based assessment thinking that frames possibilities for action across methods and settings. Copyright © 2016 National Association of Social Workers.
Keywords: *Professional Role/px [Psychology]; *Social Justice/px [Psychology]; *Social Work/mt [Methods]; *Social Workers/px [Psychology]; Adult; Female; Humans; Male; Middle Aged; Professional Role; Qualitative Research; Social Justice; Social Work; Social Workers; Social justice; Social work practice; Values; Well-being; adult; dept.swk; dual purpose; female; human; human dignity; human experiment; leadership; male; middle aged; occupation; organization; procedures; professional standard; psychology; qualitative research; social justice; social work; social work practice; social worker; thinking; wellbeing

Campaigning for social justice: increasing public access to professional social workers - Wayne, Raymie Harvard; Limone, Christine; Karp, Stephen A (Reflections: Narratives of Professional Helping, 2017)
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Getting men to explore safer sex responsibility: the use of Photovoice in health promotion research - Breny, Jean M.; Lombardi, Deirdre; Madden, Devin; Smoyer, Amy B. (SAGE Research Methods Cases: Health, 2017)
Keywords: dept.pch; dept.swk

Tools for enhancing resilience and addressing internalized heterosexism: Bibliotherapy and cinematherapy in groupwork for individuals who come out as an adult - Counselman-Carpenter, Beth; Redcay, Alex; Freeman, Amy (Groupwork, 2017)
Keywords: dept.swk; peer-reviewed

Responding to the oppression of addiction: Canadian social work perspectives - Csiernik, Rick; Rowe, William (Canadian Scholars' Press, 2017)
Uniting top academics, researchers, and practitioners, this contributed volume offers new perspectives on the meaning, role, and history of addiction in our society and the construction of illicit drug use as a social problem. This substantially revised second edition provides an authoritative focus on policy issues that will extend and enrich the education and on-going discussion of addiction within the social work community
Keywords: Canada; Social work with alcoholics; Canada; Substance abuse; Canada; Substance-Related Disorders; Social work with drug addicts; Treatment; Compulsive gambling; dept.swk; therapy; Social Work; Canada

Caring for the child welfare client: am I good enough? - Hoffler, Steven J (Smith College Studies in Social Work, 2017)
Given the demographics of youth served by the child welfare system, culturally responsive approaches are critical to effective social work practice and desperately needed. Like many adolescents who grow up in the child welfare system, Paul, a White adolescent male in foster care, was beset by a lack of adequate environmental resources and multiple stressors and had little hope or motivation to work on improving his situation. This article highlights the author's use of self as an African American male therapist who worked with Paul, using a Winnicottian and caring framework. Because child welfare workers are often overburdened by the demands of work, including large caseloads and clients with few to no resources, they find it difficult to consistently provide empathic and caring behaviors for their clients. The author highlights his therapeutic work and struggles with Paul and offers cultural insights and Winnicottian strategies when working with adolescents in the child welfare system who are ultimately in need of permanency and stability.
Keywords: Caring; Winnicott; child welfare; culture; dept.swk

Prison food in Denmark: Normal responsibility or ethnocentric imaginations? - Minke, Linda Kjær; Smoyer, Amy B. (Scandinavian penal history, culture and prison practice - Embraced by the welfare state?, 2017)
This book draws on historical and cross-disciplinary studies to critically examine penal practices in Scandinavia. The Nordic countries are often hailed by international observers as ‘model societies’, with egalitarian welfare policies, low rates of poverty, humane social policies and human rights...
Keywords: dept.swk

Indian perspectives on treating substance use disorders - Perumbilly, Sebastian A; Anderson, Stephen A (Alcoholism Treatment Quarterly, 2017)
Although research on substance use disorders (SUDs) largely focuses on the developed world, treatment programs from the developing world seldom get international attention. Focusing on India, this study was designed (1) to describe India’s treatment programs, and (2) to report Indian perspectives on critical factors related to treating SUDs. An online survey instrument was created, based on mixed-methods approach with concurrent strategies, to collect data. Participants were India’s clinicians (N = 112). Indian treatment approach suggests that SUDs must be treated by a multidisciplinary treatment team with a comprehensive plan that must include systemically focused clinical interventions in patients’/clients’ relevant relational systems. Findings may have relevance to clinicians, researchers, and policy makers globally. © 2017 Taylor & Francis.
Keywords: Addiction treatment; India; Indian; Note; adult; aged; clinical assessment; comparative study; controlled study; critical factors; dept.mft; drug dependence; family therapy; female; health survey; human; involving families; major clinical study; male; peer-reviewed; professional development; substance use disorders

Parents’ personal growth: expanding the view of therapy for child behavioral problems - Perumbilly, Sebastian A; Anderson, Stephen A; Boylin, William M (Journal of Family Psychotherapy, 2017)
Parenting literature often focuses on parental strategies that promote positive behavioral outcomes for children, but ignores key aspects of parents’ own growth process. This article presents a critical review of current literature on parenting and highlights the importance of focusing on parents’ growth in therapy. A clinical framework to define parents’ growth is offered along with case vignettes and practical guidelines for clinicians in order to assess parents’ growth. © 2017 Taylor & Francis Group, LLC.
Keywords: Article; Couple intimacy; behavior therapy; child behavior; child care; child parent relation; dept.mft; education program; family therapy; growth; human; intimacy; medical literature; parental attitude; parenting; parents’ growth; personal growth; personal needs; practice guideline; problem behavior; responsibility; self care; social isolation; training; vignette

Building a bicultural bridge - Rodriguez-Keyes, Elizabeth; Piepenbring, Julie (Smith College Studies in Social Work, 2017)
The balancing act of living between two cultures can have a significant impact on the development of adolescent Latinas living in the United States. Many adolescent Latinas, particularly second generation, live with two sets of cultural values that are often in conflict with one another. This case study illustrates the importance of understanding the impact of acculturation on the individual and the family. Issues of identity, biculturalism, and bilingualismspecifically the phenomenon of language switchingare dismantled in this case study to gain deeper insight into the unique experience that second-generation Latinas undergo when negotiating two cultural orientations. These findings are important to consider when working with the Latino population as they represent one of the largest immigrant groups and the most rapidly growing group in the United States.
Keywords: Latinas; adolescent; biculturalism; bilingual psychotherapy; cultural identity; dept.swk; language switching

Client-centered theory and the person centered approach: Values-based, evidence-supported - Rowe, William S. (Social work treatment: Interlocking theoretical approaches, 2017)
Keywords: dept.swk

Supervised injection sites: Harm reduction and health promotion - Rowe, William S.; Rapp, Lisa (Responding to the oppression of addiction: canadian social work perspectives, 2017)
Keywords: dept.swk; ⛔ No DOI found